coating
By using a coating composition containing hollow inorganic and organic spherical filler particles, the cracking, peeling and sagging of the insulating coating under high temperature and temperature changing conditions is solved, and an efficient, uniform and corrosion-resistant coating effect is achieved.
Patent Information
- Application Number
- CN202180018818.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-03
- Filing Date
- 2021-03-02
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-03-02
AI Technical Summary
The existing thermal insulation coatings are prone to cracking and peeling under high temperature and temperature changing conditions, and the coating process is time-consuming and prone to sag problems, resulting in uneven coatings and corrosion risks.
The coating compositions containing binder, curing agent, hollow inorganic spherical filler particles and hollow organic spherical filler particles are used to ensure that the volume ratio of the inorganic and organic filler particles is at least 1.1:1, combined with a thickener to improve the insulation, crack resistance and adhesion of the coating.
The crack resistance and adhesion of the coating under high temperature and temperature variation conditions is achieved, reducing the coating steps and time, reducing the risk of sagging, and improving resistance to corrosion.
Smart Images

Figure GDA0004478582120000101 
Figure GDA0004478582120000121 
Figure GDA0004478582120000181
Abstract
Description
[0001] introduction
[0002] The present invention relates to a coating composition that provides thermal insulation. The composition comprises a binder, an optional curing agent, hollow, inorganic, spherical filler particles, hollow, organic, spherical filler particles, and an optional thickener. The present invention also relates to a method for preparing the coating composition and a container for holding the composition. In addition, the present invention also relates to a method for providing a coating, preferably a thermal insulation coating, on a surface (e.g., a metal surface) and a coating formed on a surface by the composition of the present invention. Background Art
[0003] Coatings that provide thermal insulation are used in a wide variety of applications. For example, thermal insulation coatings are used in the oil and gas industry on metal pipes, tanks, and fittings, among others, where the equipment is often in contact with high temperature liquids and gases. The coating needs to have a low thermal conductivity so that adequate thermal insulation is provided. Typical coatings used today are a combination of mineral wool, glass wool, and calcium silicate, which are often covered with aluminum sheets to protect them from water and moisture.
[0004] Typically, the higher the temperature of the metal surface on which the coating is applied, the thicker the thermal insulation coating is required to achieve the necessary heat reduction over its thickness. However, the greater the thickness of the thermal insulation coating, the greater the tendency of the coating to crack, especially when exposed to temperature changes (such as a sharp increase or decrease in temperature). The occurrence of cracks in the coating also tends to cause the coating to delaminate or peel off from the metal surface (sometimes referred to as "flaking"). In addition, once a crack occurs, there is a risk of water and salt entering under the coating, creating an unfavorable environment on the metal surface. This is a well-known problem in the oil and gas industry and is generally referred to as corrosion under insulation (CUI).
[0005] The application of thicker insulating coatings is also time consuming, especially if the surface area to be coated is large (e.g., a length of pipe, or the entire surface of a tank). This is because it is usually necessary to apply a first coating layer, allow it to dry and cure, then apply a second coating layer, and so on. This must be done to avoid sagging of the coating, i.e., movement of the coating before it dries and cures. The thicker the coating layer, the greater the likelihood that it will sag, and the greater the extent to which sagging occurs. Sagging is a particular problem when coating non-horizontal, such as vertical, surfaces, and results in an unsightly, uneven coating.
[0006] Therefore, the thermal insulation coating needs to be:
[0007] Thermal insulation;
[0008] ·Resistant to peeling at high temperature;
[0009] Resistant to cracking, even during temperature changes;
[0010] Anti-sagging;
[0011] Suitable for large surface areas, such as spraying;
[0012] Resistant to water absorption causing corrosion. Summary of the invention
[0013] From a first aspect, the present invention provides a coating composition, the coating composition comprising:
[0014] (i) a binder;
[0015] (ii) optionally a curing agent;
[0016] (iii) hollow, inorganic, spherical filler particles; and
[0017] (iv) hollow, organic, spherical filler particles;
[0018] The volume ratio of the inorganic, spherical filler particles to the organic, spherical filler particles is at least 1.1:1.
[0019] Viewed from another aspect, the invention provides a process for preparing a composition as hereinbefore defined, said process comprising mixing:
[0020] (i) a binder;
[0021] (ii) optionally a curing agent;
[0022] (iii) hollow, inorganic, spherical filler particles; and
[0023] (iv) Hollow, organic, spherical filler particles.
[0024] Viewed from another aspect, the present invention provides a kit for preparing a composition as defined above, the kit comprising:
[0025] (i) a first container containing a binder, optionally hollow, inorganic, spherical filler particles, and optionally hollow, organic, spherical filler particles;
[0026] (ii) a second container containing a curing agent, optionally hollow, inorganic, spherical filler particles, and optionally hollow, organic, spherical filler particles,
[0027] wherein the hollow, inorganic, spherical filler particles and the hollow, organic, spherical filler particles are each present in at least one of the containers.
[0028] From another aspect, the present invention provides a coating composition, the coating composition comprising:
[0029] (i) a binder;
[0030] (ii) a curing agent;
[0031] (iii) hollow, inorganic, spherical filler particles;
[0032] (iv) hollow, organic, spherical filler particles; and
[0033] (v) Thickeners.
[0034] Viewed from another aspect, the invention provides a process for preparing a composition as hereinbefore defined, said process comprising mixing:
[0035] (i) a binder;
[0036] (ii) optionally a curing agent;
[0037] (iii) hollow, inorganic, spherical filler particles;
[0038] (iv) hollow, organic, spherical filler particles; and
[0039] (v) Thickeners.
[0040] Viewed from another aspect, the present invention provides a kit for preparing a composition as defined above, the kit comprising:
[0041] (i) a first container containing a binder, optionally hollow, inorganic, spherical filler particles, optionally hollow, organic, spherical filler particles, and optionally a thickener;
[0042] (ii) a second container containing a curing agent, optionally hollow, inorganic, spherical filler particles, optionally hollow, organic, spherical filler particles, and optionally a thickener,
[0043] wherein the hollow, inorganic, spherical filler particles, the hollow, organic, spherical filler particles, and the thickener are each present in at least one of the containers.
[0044] Viewed from another aspect, the invention provides a container containing a composition as hereinbefore described.
[0045] Viewed from another aspect, the invention provides a method of providing a coating on a surface, wherein the method comprises:
[0046] (i) applying the composition as described above; and
[0047] (ii) curing the composition to form a coating on the surface.
[0048] Viewed from another aspect, the invention provides a coating on a surface, preferably a metal surface, wherein the coating is formed from a composition as hereinbefore described.Preferred coatings are thermally insulating coatings or thermally insulating coatings.
[0049] Viewed from another aspect, the invention provides the use of a composition as hereinbefore described for forming a coating, preferably a thermal insulation coating, on at least one surface of an article.
[0050] Viewed from another aspect, the present invention provides a use of a composition for forming a thermal insulation coating on at least one surface of an article, preferably a metal surface, the composition comprising:
[0051] (i) a binder;
[0052] (ii) a curing agent;
[0053] (iii) hollow, inorganic, spherical filler particles; and
[0054] (iv) Hollow, organic, spherical filler particles.
[0055] Viewed from another aspect the invention provides a coating on a surface, preferably a metal surface, wherein the coating is thermally insulating, has a thickness of at least 2 mm and comprises:
[0056] (i) a binder;
[0057] (ii) a curing agent;
[0058] (iii) hollow, inorganic, spherical filler particles; and
[0059] (iv) Hollow, organic, spherical filler particles.
[0060] definition
[0061] As used herein, the term "coating composition" refers to a composition that, when applied to a surface, forms a film or coating on the surface.
[0062] As used herein, the term "binder" refers to a polymer that forms a continuous film on a substrate surface when applied to the substrate surface. The other components of the composition are dispersed in the binder. The term "organic binder" refers to a binder containing carbon.
[0063] As used herein, the term "hybrid binder" refers to a polymer formed from monomers from at least two binder classes, such as epoxy and acrylic.
[0064] As used herein, the term "epoxy" refers to a polymer or oligomer that includes epoxy groups and / or modified epoxy groups. The term epoxy adhesive covers adhesives having a traditional epoxy backbone but in which the epoxy end groups are modified with, for example, acrylic acid or methacrylic acid functional groups that can be cured with the same curing agent as the epoxy groups. Typically, epoxy resins will include at least some epoxy groups. The terms "epoxy" and "epoxide" are used interchangeably.
[0065] As used herein, the term "solid epoxy resin" refers to a polymer that is solid at 25°C and 1 atm.
[0066] As used herein, the term "liquid epoxy resin" refers to a polymer that is liquid at 25°C and 1 atm.
[0067] As used herein, the term "epoxy" refers to a three-atom cyclic ether.
[0068] As used herein, the term "epoxy adhesive system" refers to a combination of one or more epoxy resins and one or more curing agents and optionally reactive epoxy diluents, adhesion promoters and accelerators.
[0069] As used herein, the phrase "equivalent epoxy weight" or "EEW" refers to the number of epoxy equivalents in 1 kg of resin. It is measured by ASTM D-1652.
[0070] As used herein, the phrase "polysiloxane-based binder" refers to a binder comprising -Si-O- repeating units. The term polysiloxane-based encompasses binders having a conventional -Si-O- backbone but in which the end groups are modified. Polysiloxane binders may be organic or inorganic, but organopolysiloxane binders are preferred. In organopolysiloxane binders, the organic groups are present in the side chains and / or in the end groups.
[0071] As used herein, the term "curable polysiloxane binder" means that the polysiloxane-based binder includes a functional group that enables a cross-linking reaction between polysiloxane-based binder molecules or by a cross-linking agent.
[0072] As used herein, the term "polyurethane-based adhesive" refers to an adhesive having one or more diisocyanate or polyisocyanate components and a hydroxyl-functional component containing two or more hydroxyl groups as the main components (two-component system) or having one or more isocyanate prepolymers as the main components (generally one-component system). The reaction (curing) of the one or more isocyanate components and the one or more hydroxyl-functional components results in the formation of urethane functionality.
[0073] As used herein, the term "curing agent" refers to a compound that, when mixed with a binder, such as an epoxy-based binder, produces a cured or hardened coating by creating crosslinks within the polymer. Sometimes, a curing agent is referred to as a hardener.
[0074] As used herein, the terms "cure accelerator" and "accelerator" are used synonymously and refer to compounds that increase the rate of the curing reaction that causes a coating to cure or harden.
[0075] As used herein, the term "filler" refers to a compound that increases the volume or bulk of a coating composition. They are substantially insoluble in the coating composition and are dispersed therein. When filler particle size is mentioned herein, it refers to the particle size when they are added to the composition.
[0076] As used herein, the term "hollow" when used with respect to organic or inorganic spherical filler particles refers to particles having a void, cavity or empty space in the center that is occupied by a gas, typically air.
[0077] As used herein, the term "spherical" when used with respect to organic or inorganic filler particles encompasses both substantially spherical and spherical particles.Substantially spherical particles are the same size in each of the x, y and z dimensions, within ±1.2 μm, more preferably ±0.6 μm.
[0078] As used herein, if the particle size is above 5 μm, the term "average diameter" refers to the Z-average diameter determined by ISO 22412:2017 using a Malvern Mastersizer 2000.
[0079] Unless otherwise indicated, as used herein, the term "weight % (wt %)" when used with respect to individual ingredients of a composition, such as thickeners, reactive diluents, etc., refers to the actual weight of the ingredient, ie, without the presence of volatile components.
[0080] As used herein, the term "weight percent (wt %)" when used with respect to a coating composition refers to the weight relative to the total weight of the composition (ie, including non-volatile components and volatile components), unless otherwise indicated.
[0081] As used herein, the term "volatile organic compound" refers to a compound having a boiling point of ≤ 250°C at 101.3 kPa. This is the definition given in EU Directive 2004 / 42 / CE.
[0082] As used herein, the term "solvent-free" refers to a composition comprising less than 10 g / L VOC.
[0083] As used herein, the term "adhesion promoter" refers to a compound that improves the adhesion of a coating layer to a target substrate (eg, a metal substrate and / or another coating layer).
[0084] As used herein, the term "organosilane" refers to a compound including at least one Si-C bond.
[0085] As used herein, the term "anti-settling agent" refers to a compound that improves the uniformity of the consistency during storage of the coating composition. Typically, the anti-settling agent is thixotropic.
[0086] As used herein, the term "thickener" refers to a compound that increases the viscosity of a coating composition. Sometimes, thickeners are referred to as rheology modifiers.
[0087] Unless otherwise indicated, as used herein, the term "molecular weight" refers to the weight average molecular weight (Mw). It is determined by gel permeation chromatography.
[0088] As used herein, the term "density" when used with respect to hollow, spherical filler particles refers to the density as measured by a gas pycnometer. DETAILED DESCRIPTION
[0089] The present invention relates to a coating composition, comprising:
[0090] (i) a binder;
[0091] (ii) optionally a curing agent;
[0092] (iii) hollow, inorganic, spherical filler particles; and
[0093] (iv) hollow, organic, spherical filler particles;
[0094] The volume ratio of the inorganic, spherical filler particles to the organic, spherical filler particles is at least 1.1:1.
[0095] Preferably, the coating composition of the present invention is solvent-free. Particularly preferably, the composition comprises 0-10 g / L VOC, more preferably 0-5 g / L VOC, and still more preferably 0-2.5 g / L VOC.
[0096] Optionally, the coating composition of the present invention further comprises: (v) a thickener; (vi) an adhesion promoter; (vii) a reactive diluent; and / or (viii) an additive.
[0097] The coating compositions of the present invention provide coatings with high insulation levels, which means that the coating thickness required to achieve adequate insulation is minimized. Advantageously, the coatings formed by the coating compositions of the present invention have crack resistance and excellent adhesion to the underlying surface (e.g., metal surfaces, such as primed metal surfaces) even during exposure to high temperatures (e.g., 150° C.) and thermal shocks (e.g., directly from 150 to -20° C.) and temperature cycles (e.g., between -20 and 60° C.). Therefore, the coatings formed by the coating compositions of the present invention have a lower tendency to peel or flake off from the underlying surface to which they are applied than conventional coatings. When combined, the improved crack resistance and improved adhesion of the coatings of the present invention mean that the coatings more effectively protect the underlying substrate (e.g., metal substrate) from corrosion.
[0098] Advantageously, the coating composition of the present invention also has a high level of anti-sagging. This is very beneficial because it means that a thicker coating layer can be applied in a single step, which means that a thicker coating can be prepared in a smaller number of steps. This benefit is particularly useful when coating large non-horizontal surfaces such as tank walls.
[0099] Binder
[0100] The coating composition of the present invention comprises a binder. The type of binder present depends mainly on the environment in which the coating will ultimately be present, in particular the temperature of the environment and the corrosiveness of the environment. Preferably, the binder is an organic binder.
[0101] Examples of suitable binders that may be present in the coating composition of the present invention include epoxy, preferably epoxy resin, acrylic, alkyd, phenolic, silicone, polysiloxane, polyurethane, polyurea, polyaspartic acid, and hybrids and mixtures thereof. Preferably, the binder is selected from epoxy (e.g. epoxy), polysiloxane (e.g. polysiloxane), polyurethane (e.g. polyurethane), polyurea, and hybrids and mixtures thereof.
[0102] Preferably, the binder present in the coating composition is an organic binder or a polysiloxane-based binder. More preferably, the binder is an organic binder. Still more preferably, the binder is an organic binder selected from epoxy-based, more preferably epoxy resin, polysiloxane-based, polyurethane and hybrids and mixtures thereof.
[0103] The total amount of binder present in the coating composition of the present invention is preferably 10-70 wt%, more preferably 15-60 wt%, still more preferably 15-50 wt%, and even more preferably 20-40 wt%, based on the total weight of the coating composition.
[0104] Epoxy adhesive
[0105] In a preferred coating composition of the present invention, the organic binder is epoxy-based, and preferably an epoxy resin. Optionally, the epoxy-based binder is modified with fatty acid, polypropylene oxide and / or polyethylene oxide.
[0106] The epoxy adhesive, such as an epoxy resin adhesive, may be a liquid epoxy adhesive or a solid epoxy adhesive, or a combination thereof. However, preferably, the epoxy adhesive is a liquid epoxy adhesive. If the epoxy adhesive is a liquid, its viscosity is preferably 1000-20000 mPa, more preferably 1500-15000 mPas, still more preferably 1500-10000 mPas, and even more preferably 2000-6500 mPas.
[0107] The preferred epoxy binder, such as an epoxy resin binder, present in the coating composition of the present invention has an equivalent epoxy weight (EEW) of 150-2000 g / eq, more preferably 155 to 1500 g / eq, still more preferably 160-1000 g / eq, and still more preferably 160-300 g / eq. The level of EEW is important for achieving an optimal mixing ratio (e.g., 1:1 to 4:1, such as 3:1 volume solids) between the epoxy binder and the curing agent. It is well known that binders with low Mw (usually associated with low EEW) have lower viscosities and therefore require less solvent for formulation. This is beneficial for achieving low VOC content or solvent-free compositions.
[0108] The equivalent epoxy weight (EEW) of the preferred epoxy liquid adhesive is 156 to 1000. The EEW of the more preferred epoxy liquid adhesive is less than 300, more preferably 156 to 300, and still more preferably 156 to 250. The equivalent epoxy weight (EEW) of the preferred epoxy solid adhesive is 300 to 1000, more preferably 350 to 750, still more preferably 400 to 700, and particularly preferably 500 to 670.
[0109] Preferred epoxy adhesives include more than one epoxy group per molecule. Such epoxy groups may be located at internal or terminal positions on the epoxy adhesive, or on a ring structure incorporated into the epoxy adhesive. Preferably, the epoxy adhesive includes at least two epoxy groups so that a cross-linked network can be formed.
[0110] Preferably, the coating composition of the present invention comprises one or more epoxy-based binders selected from aromatic epoxy-based binders, aliphatic epoxy-based binders and alicyclic epoxy-based binders.
[0111] Representative examples of aliphatic and alicyclic epoxy-based binders suitable for use in the composition of the present invention include hydrogenated bisphenol A, hydrogenated bisphenol A novolac, and dicyclopentadiene-based binders, glycidyl ethers (such as polyglycidyl ethers of polyhydric alcohols), epoxy-functional acrylic resins, and any hybrids or mixtures thereof. Modified, especially acrylic or methacrylic modified hydrogenated bisphenol A, hydrogenated bisphenol A novolac, dicyclopentadiene-based binders, glycidyl ethers (such as polyglycidyl ethers of polyhydric alcohols) are also preferred.
[0112] Preferably, the coating composition of the present invention comprises an aromatic epoxy-based binder, such as an aromatic epoxy resin binder. Preferably, the aromatic epoxy-based binder is derived from a combination of a compound comprising at least one epoxide functionality and an aromatic co-reactant comprising at least two hydroxyl groups.
[0113] Representative examples of aromatic epoxy adhesives suitable for use in the composition of the present invention include: bisphenol epoxy adhesives, such as bisphenol A, bisphenol F and bisphenol S, resorcinol diglycidyl ether (RDGE), novolac epoxy adhesives, such as phenol novolac adhesives (bisphenol A novolac, bisphenol S novolac) and cresol novolac adhesives, and hybrids or mixtures thereof. Modified, especially acrylic or methacrylic modified bisphenol A, bisphenol F and bisphenol S, resorcinol diglycidyl ether (RDGE), novolac epoxy adhesives (such as phenol novolac adhesives (bisphenol A novolac, bisphenol S novolac) and cresol novolac adhesives are also preferred.
[0114] Preferred examples of epoxy adhesives used in the composition of the present invention are bisphenol A adhesives, 4,4'-isopropyldiphenol-epichlorohydrin adhesives, bisphenol F adhesives, novolac adhesives, and hybrids and mixtures thereof. Particularly preferred epoxy adhesives are bisphenol A adhesives, bisphenol F adhesives, and hybrids and mixtures thereof. In some compositions, the adhesive is preferably a bisphenol A epoxy resin adhesive. In other compositions, the adhesive is preferably a bisphenol F epoxy resin adhesive. In other compositions, the adhesive is preferably a mixture of a bisphenol A epoxy resin adhesive and a bisphenol F epoxy resin adhesive.
[0115] Bisphenol A epoxy-based adhesives are known to those skilled in the art and have the following general structure.
[0116]
[0117] Particularly preferred coating compositions of the present invention include one or more bisphenol F epoxy-based binders. Combinations of two or more bisphenol F binders may optionally be used. It has been found that bisphenol F epoxy-based binders reduce the viscosity of the coating composition relative to coating compositions containing the more commonly used bisphenol A epoxy-based binders. This in turn enables the preparation of high solids, solvent-free coating compositions, thereby reducing VOCs.
[0118] The EEW of the preferred bisphenol F epoxy adhesive is 100-350. More preferably, the EEW is 300 or less, such as 100-300, more preferably 150 to 250. The preferred bisphenol F epoxy adhesive is a liquid. The viscosity of the bisphenol F epoxy adhesive is preferably 1000-10000 mPas, and more preferably 2000-5000 mPas.
[0119] The preferred bisphenol F (4',4'-methylene bisphenol) epoxy adhesive is derived from a combination of bisphenol F and epichlorohydrin. The use of a difunctional epoxy bisphenol F adhesive is particularly preferred.
[0120] The solid content of the epoxy adhesive is preferably greater than 70% by weight, preferably greater than 80% by weight, preferably greater than 90% by weight, preferably greater than 99% by weight. Particularly preferably, the epoxy adhesive is solvent-free.
[0121] Epoxy-based binders suitable for the coating composition of the present invention are commercially available. Examples of commercially available epoxy-based binders suitable for the coating composition include:
[0122] Bisphenol A epoxy adhesives: Epikote 828, Epikote 1004, Epikote 1001 X 75 and Epikote 1009 from Hexion. Araldite GY 250, Araldite GZ 7071X75BD and Araldite GZ 7071X75CH from Huntsman Advanced Materials. DER 664-20 and DER 684-EK40 from Dow Chemicals.
[0123] Bisphenol F epoxy adhesives: Epikote 862 from Hexion, YDF-170 from Kukdo, GY285 from Huntsman, DER 354 from Dow, BFE-170 from CCP, or KF8100 from Kolon; and
[0124] • Mixtures of bisphenol A and bisphenol F: DER 352 and DEN 438-X 80 from Dow Chemicals, Epikote 235 from Hexion.
[0125] The coating composition of the present invention may contain one or more epoxy binders. If both a liquid epoxy binder and a solid epoxy binder are present in the coating composition, it is preferred that the liquid epoxy binder is in excess relative to the solid epoxy binder.
[0126] The epoxy-based binder (i.e., liquid and solid) present in the coating composition of the present invention is preferably 10-60 wt %, more preferably 15-70 wt %, still more preferably 15-50 wt %, and still more preferably 20-40 wt %, based on the total weight of the coating composition.
[0127] Polysiloxane adhesive
[0128] The silicone-based binder present in the coating composition of the present invention may be any curable silicone-based binder.Silicone-based binders are particularly useful in coatings for insulating articles such as cans or pipes at very high temperatures, for example temperatures in excess of 100°C.
[0129] The polysiloxane-based adhesive is preferably an organopolysiloxane with a curing reactive functional group of terminal and / or pendant. A minimum of two curing reactive functional groups per molecule is preferred. Examples of curing reactive functional groups are silanol, alkoxy, acetoxy, alkenyloxy, ketoxime, alcohol, amine, epoxy and / or isocyanate. Preferred polysiloxane-based adhesives contain curing reactive functional groups selected from silanol, alkoxy or acyloxy groups. The curing reaction is generally a condensation curing reaction. The polysiloxane-based adhesive optionally includes more than one type of curing reactive group, and can be cured, for example, by both condensation curing and amine / epoxy curing.
[0130] The polysiloxane-based binder present in the coating composition of the present invention preferably comprises at least 30 wt% polysiloxane moieties, preferably greater than 50 wt% polysiloxane moieties, and still more preferably greater than 70 wt% polysiloxane moieties, such as more than 99.99 wt% polysiloxane moieties. Optionally, the polysiloxane-based binder is pure polysiloxane.
[0131] The polysiloxane moiety is defined as a repeating unit containing the motif -Si-O- based on the gross weight of the polysiloxane-based binder. The weight % of the polysiloxane moiety can be determined based on the stoichiometric weight ratio of the starting materials in the polysiloxane synthesis. Alternatively, the polysiloxane content can be determined using analytical techniques such as IR or NMR. Information about the weight % of the polysiloxane moiety in commercially available polysiloxane-based binders can be easily obtained by suppliers.
[0132] It should be understood that the polysiloxane-based binder may consist of a single repeating sequence of siloxane units, or may be interrupted by non-siloxane moieties such as organic moieties. The organic moieties may include, for example, alkylene, arylene, polyalkylene oxide, amide, thioether, or a combination thereof, preferably, the organic moieties may include, for example, alkylene, arylene, polyalkylene oxide, amide, or a combination thereof.
[0133] In a preferred coating composition of the present invention, the polysiloxane-based binder includes amine functional groups in terminal or pendant positions.
[0134] The polysiloxane-based binder may be composed of only one type of polysiloxane or a mixture of different polysiloxanes.
[0135] In a preferred coating composition, the polysiloxane-based binder is a branched polysiloxane-based binder.
[0136] A preferred polysiloxane-based binder present in the coating composition of the present invention is represented by the following formula (D1):
[0137]
[0138] in
[0139] Each R 1 Independently selected from hydroxyl, C 1-6 -alkoxy, C 1-6 -Hydroxyl, C 1-6 -epoxy groups, C 1-6 Amine, C 1-10 Alkyl, C 6-10 Aryl, C 7-10 Alkyl aryl or O-Si(R 5 ) 3-z (R 6 ) z;
[0140] Each R 2 Independently selected from C 1-10 Alkyl, C 6-10 Aryl, C 7-10 Alkyl aryl or polyalkylene oxide and / or about R 1 The group substituted C1-6 alkyl;
[0141] Each R 3 and R 4 Independently selected from C 1-10 Alkyl, C 6-10 Aryl, C 7-10 Alkyl aryl or polyalkylene oxide substituted C 1-6 alkyl;
[0142] Each R 5 are independently hydrolyzable groups, such as C 1-6 Alkoxy, acetoxy, alkenyloxy or ketoxy;
[0143] Each R 6 are independently selected from unsubstituted or substituted C 1-6 alkyl;
[0144] z is 0 or an integer from 1 to 2;
[0145] x is an integer of at least 2;
[0146] y is 0 or an integer of at least 1.
[0147] Preferably, R 1 Selected from hydroxyl and O-Si(R 5 ) 3-z (R 6 ) z , where R 5 C 1-6 Alkoxy, R 6 C 1-6 alkyl, and z is 0 or an integer from 1 to 2. More preferably, R 1 Selected from hydroxyl and O-Si(R 5 ) 3-z (R 6 ) z , where R 5 C 1-3 Alkoxy, R 6 C 1-3 An alkyl group, and z is 0 or an integer of 1-2.
[0148] Preferably, R 2 C 1-10 Alkyl, C 6-10 Aryl, C 7-10 Alkyl aryl or O-Si(R 5 ) 3-z (R 6 ) z .
[0149] Preferably, R 3 C1-10 Alkyl or C 6-10 More preferably, R 3 C 1-4 Alkyl or C 6 Aryl, still more preferably C 1-2 Alkyl or C 6 An aryl group, and still more preferably a methyl group or a phenyl group.
[0150] Preferably, R 4 C 1-10 Alkyl or C 6-10 More preferably, R 3 C 1-4 Alkyl or C 6 Aryl, still more preferably C 1-2 Alkyl or C 6 An aryl group, and still more preferably a methyl group or a phenyl group.
[0151] In a preferred coating composition, the polysiloxane-based binder of the present invention is a branched polysiloxane comprising methyl, phenyl and methoxy groups.
[0152] The weight average molecular weight of the polysiloxane-based binder present in the coating composition of the present invention is preferably 400-150,000 g / mol, more preferably 1000-120,000 g / mol, and still more preferably 5000-110,000 g / mol.
[0153] Suitable polysiloxane-based binders for use in the coating composition of the present invention are commercially available. Representative commercially available polysiloxane-based binders include REN 50 and REN 80 from Wacker, Silikophen P50X and Silikophen P80X from Evonik.
[0154] Preferred coating compositions of the present invention comprise 10-60 wt% polysiloxane based binder, more preferably 15-70 wt% polysiloxane based binder, and still more preferably 15-50 wt% polysiloxane based binder, based on the total dry weight of the composition.
[0155] Polyurethane adhesive
[0156] In preferred coating compositions of the present invention, the organic binder is polyurethane based, and preferably polyurethane.
[0157] A preferred polyurethane-based binder used in the coating composition of the present invention comprises a) a polyisocyanate component and b) a hydroxyl-functional component comprising at least two hydroxyl groups. Crosslinking results from the reaction between the polyisocyanate component a) and the hydroxyl-functional component b).
[0158] Polyisocyanates suitable for use as the polyisocyanate component a) in the coating composition are well known in the art. Examples of suitable low molecular weight polyisocyanates having a molecular weight of 168 to 300 g / mol include: hexamethylene diisocyanate (HDI), 2,2,4- and / or 2,4,4-trimethyl-1,6-hexamethylene diisocyanate, dodecamethylene diisocyanate, 2,4-diisocyanato-1-methyl-benzene (toluene diisocyanate, TDI), 2,4-diisocyanato-1-methylbenzene, 1,4-diisocyanatocyclohexane, 1-isocyanato-3,3 ,5-trimethyl-5-isocyanatomethylcyclohexane (IPDI), 2,4'- and / or 4,4'-diisocyanato-dicyclohexylmethane, 2,4- and / or 4,4'-diisocyanato-diphenylmethane, and mixtures of these isomers with their higher homologues (the higher homologues are obtained in a known manner by phosgenation of aniline / formaldehyde condensates), 2,4- and / or 2,6-diisocyanatotoluene and any mixtures of these compounds.
[0159] In some preferred coating compositions of the present invention, the polyisocyanate component a) is selected from: aliphatic polyisocyanates, such as hexamethylene diisocyanate (HDI), 2,2,4- and / or 2,4,4-trimethyl-1,6-hexamethylene diisocyanate, dodecamethylene diisocyanate, 1,4-diisocyanatocyclohexane, 1-isocyanato-3,3,5-trimethyl-5-isocyanatomethylcyclohexane (IPDI), 2,4'- and / or 4,4'-diisocyanato-dicyclohexylmethane and 2,4- and / or 4,4'-diisocyanato-diphenylmethane.
[0160] In other preferred coating compositions according to the invention, the polyisocyanate component a) is selected from the group consisting of aromatic polyisocyanates, for example 2,4-diisocyanato-1-methyl-benzene (toluene diisocyanate, TDI), 2,4-diisocyanato-1-methyl-benzene, and mixtures of these isomers with their higher homologues which are obtained in a known manner by phosgenation of aniline / formaldehyde condensates, 2,4- and / or 2,6-diisocyanatotoluene and any mixtures of these compounds.
[0161] In preferred coating compositions of the present invention, the polyisocyanate component a) is a derivative of the above-mentioned monomeric polyisocyanates, as is conventional in the art. These derivatives include polyisocyanates containing biuret groups. Examples of particularly preferred derivatives include N,N',N"-tris-(6-isocyanatohexyl)-biuret and mixtures thereof with its higher homologues, and N,N',N"-tris-(6-isocyanatohexyl)-isocyanurate and mixtures thereof with its higher homologues containing more than one isocyanurate ring.
[0162] Examples of suitable commercially available polyisocyanates are:
[0163] Desmodur N3900 (formerly VP2410), from Bayer (Germany), aliphatic polyisocyanate
[0164] Desmodur N3600, from Bayer (Germany), aliphatic polyisocyanate
[0165] Desmodur N3800, from Bayer (Germany), aliphatic polyisocyanate
[0166] Tolonate HDT-LV2, from Rhodia (France), aliphatic polyisocyanate
[0167] Desmodur N3390, from Bayer (Germany), aliphatic polyisocyanate
[0168] Tolonate HDT90, from Rhodia (France), aliphatic polyisocyanate
[0169] Basonat HI 190B / S, from BASF (Germany), aliphatic polyisocyanate
[0170] Desmodur N75, from Bayer (Germany), aliphatic polyisocyanate
[0171] Bayhydur VP LS2319, from Bayer (Germany), aliphatic polyisocyanate
[0172] Tolonate IDT 70B, from Rhodia (France), aliphatic polyisocyanate
[0173] Desmodur H, from Bayer (Germany).
[0174] Basonat HB 175MP / X BASF-Germany, aliphatic polyisocyanate
[0175] Examples of suitable commercially available aromatic polyisocyanate resins are:
[0176] Desmodur L67 BA (Bayer Material Science)
[0177] Desmodur E21 (Bayer Material Science)
[0178] Desmodur VL (Bayer Material Science)
[0179] Voratron EC 112 (Dow Chemicals)
[0180] Desmodur E23 (Bayer Material Science)
[0181] Desmodur E 1660 (Bayer Material Science)
[0182] Suprasec 2495 (Huntsman Advanced Materials).
[0183] Prepolymers and semi-prepolymers containing isocyanate groups based on the abovementioned monomeric polyisocyanates and organic polyhydroxy compounds are also preferably used as polyisocyanate component a). These prepolymers and semi-prepolymers generally have an isocyanate content of 0.5 to 30% by weight, preferably 1 to 20% by weight, and are prepared in a known manner by reaction of the abovementioned starting materials in an NCO / OH equivalent ratio of 1.05:1 to 10:1, preferably 1.1:1 to 3:1, optionally after this reaction by distillative removal of any unreacted volatile starting polyisocyanates still present.
[0184] Prepolymers and semi-prepolymers can be prepared from polyols having a molecular weight of 62 to 299 g / mol. Examples include: ethylene glycol, propylene glycol, trimethylolpropane, 1,6-dihydroxyhexane; low molecular weight hydroxyl-containing esters of these polyols with dicarboxylic acids of the type exemplified below; low molecular weight ethoxylated and / or propoxylated products of these polyols; and mixtures of the aforementioned polyhydric modified or unmodified alcohols.
[0185] Preferably, the prepolymers and semi-prepolymers are prepared from relatively high molecular weight polyols. These polyols have at least two hydroxyl groups per molecule and more preferably have a hydroxyl content of 0.5-17 wt%, preferably 1-5 wt%.
[0186] Examples of commercially available polyesterols include:
[0187] Desmophen 651 MPA from Bayer (Germany)
[0188] Desmophen VP LS 2089 from Bayer Material Science (Germany)
[0189] The polyether alcohols obtained in a known manner by alkoxylation of suitable starter molecules are also suitable for preparing prepolymers and semi-prepolymers containing isocyanate groups. Examples of suitable starter molecules for polyether polyols include the aforementioned monomeric polyols, water and any mixtures thereof. Ethylene oxide and / or propylene oxide are particularly suitable alkylene oxides for the alkoxylation reaction. These alkylene oxides can be introduced into the alkoxylation reaction one after the other or as a mixture.
[0190] Examples of commercially available polyether polyols include:
[0191] Desmophen 1380 BT 03 / 2008 (formerly Desmophen 550U) from Bayer Material Science (Germany)
[0192] Voranol CP 450 Polyol from Dow Chemicals (Germany)
[0193] Hydroxyl-containing polycarbonates which can be prepared by reaction of the aforementioned monomeric diols with phosgene and diaryl carbonates, such as diphenyl carbonate, are also suitable for preparing the prepolymers and semi-prepolymers.
[0194] Preferably, component b) is based wholly or partly on organic polyols and comprises both low molecular weight polyols and higher molecular weight polyols as described above with respect to the preparation of prepolymers and semi-prepolymers suitable for use as polyisocyanate component a).
[0195] Particularly preferred hydroxy-functional, isocyanate-reactive compounds which can be used as component b) are the hydroxy-functional polyacrylates known for polyurethane coatings. These compounds are hydroxyl-containing copolymers of olefinically unsaturated compounds having a number average molecular weight (Mn) determined by vapor pressure or membrane osmotic pressure measurement of 800 to 50,000, preferably 1000 to 20,000, and more preferably 5000 to 10,000, and a hydroxyl content of 0.1 to 12% by weight, preferably 1 to 10% by weight, and most preferably 2 to 6% by weight. The copolymers are based on hydroxyl-containing olefinic monomers and hydroxyl-free olefinic monomers. Examples of suitable monomers include: vinyl and vinylidene monomers, such as styrene, α-methylstyrene, o- and p-chlorostyrene, o-, m- and p-methylstyrene, and p-tert-butylstyrene; acrylic acid; (meth)acrylonitrile; acrylic and methacrylic esters of alcohols containing 1 to 8 carbon atoms, such as ethyl acrylate, methyl acrylate, n- and isopropyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, isooctyl acrylate, methyl methacrylate, ethyl methacrylate , butyl methacrylate and isooctyl methacrylate; diesters of fumaric acid, itaconic acid or maleic acid having 4 to 8 carbon atoms in the alcohol component; (meth)acrylic acid amides; vinyl esters of alkane monocarboxylic acids having 2 to 5 carbon atoms, such as vinyl acetate or vinyl propionate; and hydroxyalkyl esters of acrylic acid or methacrylic acid having 2 to 4 carbon atoms in the hydroxyalkyl group, such as 2-hydroxyethyl ester, 2-hydroxypropyl ester, 4-hydroxybutyl ester of acrylic acid and methacrylic acid, respectively, and trimethylolpropane-monoester or pentaerythritol-monoester of acrylic acid or methacrylic acid. Mixtures of the aforementioned monomers can also be used for the preparation of hydroxy-functional polyacrylates. Mixtures of the polyol compounds described above can also be used as component b).
[0196] In preferred polyurethane-based binders, components a) and b) are used in amounts sufficient to provide an equivalent ratio of isocyanate groups to isocyanate-reactive (hydroxyl) groups of 0.8:1 to 20:1, preferably 0.8:1 to 2:1, more preferably 0.8:1 to 1.5:1, even more preferably 0.8:1 to 1.2:1, and most preferably about 1:1. The hydroxyl-functional compound b) is preferably present in an amount such that up to 20 hydroxyl groups are present. Preferably, the equivalent ratio of hydroxyl groups to secondary amino groups is from 10:1 to 1:10.
[0197] Examples of suitable commercially available hydroxy-functional (isocyanate-reactive) resins include:
[0198] Synocure 878 N 60, from Arkem (Spain), a hydroxy-functional acrylic resin in an aromatic hydrocarbon.
[0199] Synthalat A 0 77, from Synthopol Chemie (Germany)
[0200] Synthalat A 045, from Synthopol Chemie (Germany)
[0201] Synthalat A 088MS, from Synthopol Chemie (Germany)
[0202] Synthalat A 141HS 05, from Synthopol Chemie (Germany)
[0203] Synthalat A 060, from Synthopol Chemie (Germany)
[0204] Desmophen A XP 2412 from Bayer Material Science (Germany)
[0205] Synthalat A-TS 1603, from Synthopol Chemie (Germany)
[0206] Acrylamac 332-2629, from Momentive (Germany)
[0207] Polyurea adhesive
[0208] In some preferred coating compositions of the present invention, the organic binder is a polyurea binder, and preferably a polyurea. The polyurea binder includes a diisocyanate or polyisocyanate component and an amine functional component containing at least two amine groups.
[0209] Polyisocyanates suitable for use in coating compositions are well known in the art. Examples of suitable polyisocyanates are as described above with respect to the polyurethane-based binder.
[0210] The amine groups in the amine functional component are preferably primary or secondary amine groups. More preferably, the amine groups are secondary amine groups.
[0211] Particularly preferably, the amine groups have been pre-reacted with esters of, for example, maleic acid and fumaric acid to form polyaspartic acid ester derivatives. Preferred polyaspartic acid ester derivatives are represented by the following formula:
[0212]
[0213] in
[0214] X represents an organic group which is inert towards isocyanate groups at a temperature not exceeding 100° C.;
[0215] Each R 1 and R 2 independently selected from organic groups which are inert towards isocyanate groups at temperatures not exceeding 100°C;
[0216] Each R 3 and R 4 independently selected from hydrogen and organic groups that are inert toward isocyanate groups at temperatures not exceeding 100°C;
[0217] n is an integer of at least 2.
[0218] Examples of suitable amine-functional components include: ethylenediamine, 1,2-diaminopropane, 1,4-diaminobutane, 1,6-diaminohexane, 2,5-diamino-2,5-dimethylhexane, 2,2,4- and / or 2,4,4-trimethyl-1,6-diaminohexane, 1,11-diaminoundecane, 1,12-diaminoundecane, 1-amino-3,3,5-trimethyl-5-aminomethyl-cyclohexane, 2,4 and / or 2,6-hexahydrotoluenediamine, 2,4'- and / or 4,4'-diamino-dicyclohexylmethane and 3,3'-dimethyl-4,4'-diamino-dicyclohexylmethane. Aromatic polyamines such as 2,4- and / or 2,6-diaminotoluene and 2,4'- and / or 4,4'-diaminophenylmethane are also suitable. Polyether polyamines can also be used.
[0219] Curing agent
[0220] The coating composition of the present invention optionally contains a curing agent. When the binder is selected from epoxy, preferably epoxy resin, phenolic, silicone, polysiloxane, polyurethane, polyurea, polyaspartic acid, and hybrids and mixtures thereof, the coating composition preferably contains a curing agent. When the binder is an acrylic binder or an alkyd binder, a curing agent is optionally present.
[0221] When present, the curing agent reacts with the binder, such as an epoxy-based binder, during curing to form a coating, such as a film coating. Therefore, the curing agent is conducive to providing a coating composition with an acceptable curing time. In a preferred coating composition of the present invention, the curing agent cures the binder at a temperature in the range of -5-50°C, more preferably 0-40°C. Preferably, the curing agent cures at ambient temperature. The ambient temperature of the environment is variable, depending on, for example, the geographical location, and can be -5-50°C. An advantage of the coating composition of the present invention is that it is curable within this range, i.e., -5-50°C. Unlike many known coating compositions, it does not need to be cured in an oven.
[0222] Conventional curing agents may be used in the coating composition of the present invention.
[0223] The total amount of the binder and the curing agent(s) in the coating composition of the present invention is preferably 20% to 80% by weight, more preferably 30% to 70% by weight, and still more preferably 40% to 60% by weight, based on the total weight of the coating composition. The total amount of the curing agent(s) in the coating composition of the present invention is preferably 10% to 40% by weight, and still more preferably 15% to 30% by weight, based on the total weight of the coating composition.
[0224] Curing agent for epoxy adhesives
[0225] In order to obtain a crosslinked network with the epoxy-based binder, the curing agent must contain at least two "reactive" hydrogen atoms. The term "reactive" refers to hydrogen atoms that can be transferred from a nucleophile to an oxygen atom of the epoxide during a ring-opening reaction. The curing agent generally contains at least two curing reactive functional groups. Preferably, the curing agent contains at least two reactive hydrogen atoms connected to nitrogen.
[0226] Representative examples of the class of suitable curing agents that can be used for epoxy-based adhesives include mercaptan curing agents, polythiol curing agents, amine curing agents, polyamine curing agents and / or amino-functional polymer curing agents. Curing agents can also alternatively include at least one amino-functional polysiloxane. The coating composition of the present invention can include a mixture of curing agents.
[0227] An example of a suitable polythiol curing agent includes pentaerythritol tetramercaptopropionate. An example of a suitable commercially available polythiol curing agent is GARBIN® from Gabriel Performance Materials GPM800.
[0228] Preferred coating compositions of the present invention comprise an amine curing agent, a polyamine curing agent or an amino-functional polymeric curing agent or a mixture thereof. More preferably, the coating composition comprises at least one amine-functional curing agent.
[0229] Preferably, the curing agent contains at least two amine groups. The amine groups can be primary amine groups or secondary amine groups.
[0230] Suitable amine, polyamine and amino-functional polymer curing agents are selected from aliphatic amines and polyamines (e.g., cycloaliphatic amines and polyamines), polyamidoamines, polyamide amines, polyoxyalkyleneamines (e.g., polyoxyalkylene diamines), alkyleneamines (e.g., alkylene diamines), aralkylamines, aromatic amines, Mannich bases (e.g., those commercially sold as "phenalkamine"), amino-functional silicones or silanes, and epoxy adducts and derivatives thereof. The adducts can be prepared by reaction of amines with suitably reactive compounds such as epoxy binders, epoxy-functional reactive diluents, acrylates, maleates, fumarates, methacrylates or electrophilic vinyl compounds such as acrylonitrile. Preferred amine, polyamine and amino-functional polymer curing agents are selected from aliphatic amines and polyamines (e.g., cycloaliphatic amines and polyamines), polyamidoamines, polyoxyalkyleneamines (e.g., polyoxyalkylene diamines), alkyleneamines (e.g., alkylene diamines), aralkylamines, aromatic amines, Mannich bases (e.g., those commercially sold as "phenalkamine"), amino-functional silicones or silanes, and epoxy adducts and derivatives thereof. The adducts can be prepared by reaction of amines with suitably reactive compounds such as epoxy binders, epoxy-functional reactive diluents, acrylates, maleates, fumarates, methacrylates or electrophilic vinyl compounds such as acrylonitrile.
[0231] Examples of suitable commercially available amine functional curing agents include:
[0232] Sunmide CX-105X from Evonik 2165, Ancamine 2280, Ancamine 2432, Ancamine 2519, Ancamine 2802, Ancamine 2609w, Ancamine 2806;
[0233] Epikure 3090, Epikure 3140 and Epikure 3115-X-70 from Hexion;
[0234] Mannich base AP1077 from Admark Polycoats;
[0235] MXDA and Gaskamine 240 from Mitsubishi Gas Chemical Company Inc; and
[0236] Aradur 42BD and Aradur 943CH from Huntsman Advanced Materials.
[0237] Particularly preferably, the curing agent is a cyclic amine functional curing agent.
[0238] In a preferred coating composition of the present invention comprising an epoxy-based binder, the curing agent is a phenalkamine curing agent. Phenalkamine is obtained from cardanol, which is a major component of cashew nut shell liquid. Phenalkamine includes aliphatic or alicyclic polyamine substituents attached to aromatic rings. Suitable commercially available phenalkamine curing agents are available from Cardolite. Examples include Cardolite NC 541, Cardolite Lite 2001, and Cardolite Lite 2002.
[0239] In another preferred coating composition of the present invention comprising an epoxy-based binder, the curing agent is an aliphatic and / or cycloaliphatic polyamine, such as Ancamine curing agent from Evonik. Cycloaliphatic polyamine curing agents are particularly preferred. Specific examples of the alicyclic polyamine curing agent include 1,4-cyclohexanediamine, diaminodicyclohexylmethane (particularly, 4,4'-methylenebiscyclohexylamine), 2,2'-dimethyl-4,4'-methylenebiscyclohexylamine, 4,4'-isopropylidenebiscyclohexylamine, norbornanediamine, bis(aminomethyl)cyclohexane, isophoronediamine, menthenediamine (MDA), 2,5-bis(4-aminocyclohexylmethyl)cyclohexylamine, 4-(p-aminobenzyl)cyclohexylamine, 2,4'-bis(4"-aminocyclohexyl)-2',4-methylenedianiline, 4-[(4-aminocyclohexyl)methyl]-[4-[(4-aminocyclohexyl)methyl]cyclohexyl]-cyclohexylamine, 2,4-bis(4-aminocyclohexylmethyl)aniline, and 2,5-bis(4-aminocyclohexylmethyl)aniline.
[0240] Mixtures of two or more curing agents may also be used, such as a cycloaliphatic and an aliphatic curing agent, two or more cycloaliphatic curing agents, an aromatic and a cycloaliphatic curing agent, a mixture of an aromatic and an aliphatic curing agent, and the like.
[0241] The curing agent can be supplied neat or in a solvent. Preferably, however, the curing agent is solvent-free. A key parameter of the curing agent is its viscosity. Preferably, the viscosity of the curing agent is less than 1000 mPas, more preferably less than 700 mPas. Such a viscosity facilitates the incorporation of larger amounts of hollow, spherical fillers, thereby improving thermal insulation.
[0242] In terms of the term "active hydrogen equivalent weight", the equivalent weight of the curing agent is generally referenced in the art. The amount of "active hydrogen equivalent" with respect to one or more curing agents is the sum of the contributions of each of the one or more curing agents. The contribution of each of the one or more curing agents to the active hydrogen equivalent is defined as the number of grams of curing agent divided by the active hydrogen equivalent weight of the curing agent, wherein the active hydrogen equivalent weight of the curing agent is determined as follows: the number of grams of curing agent equivalent to 1 mole of active hydrogen. For adducts with epoxy-based binders, the contribution of the reactants prior to addition is used to determine the amount of "active hydrogen equivalent" in the entire epoxy-based binder system.
[0243] It is also common to quote the number of "epoxy equivalents" in epoxy adhesives. "Epoxy equivalents" is the sum of the contributions of each of the one or more epoxy adhesives and any other components containing epoxy groups, such as silanes or reactive diluents. The contribution of each of the one or more epoxy adhesives to the epoxy equivalent is defined as the number of grams of epoxy adhesive divided by the epoxy equivalent weight of the epoxy adhesive, where the epoxy equivalent weight of the epoxy adhesive is determined as follows: the number of grams of epoxy resin equivalent to 1 mole of epoxy groups. For adducts with epoxy adhesives, the contribution of the reactants before addition is used to determine the number of "epoxy equivalents" in the epoxy adhesive system.
[0244] In the preferred coating composition of the present invention, the ratio between the hydrogen equivalent of the total curing agent and the total epoxy equivalent in the epoxy-based binder system of the present invention is in the range of 50:100 to 120:100. In addition, in the preferred epoxy-based binder system, the ratio between the hydrogen equivalent of the curing agent and the epoxy equivalent of the epoxy resin is in the range of 60:100 to 130:100, such as in the range of 80:100 to 120:100, for example, in the range of 90:100 to 110:100.
[0245] It will be appreciated that the curing agent is kept separate from the binder (e.g., epoxy-based binder) and is mixed therewith only shortly before application to the surface. The mixing ratio of the binder (e.g., epoxy-based binder) and the curing agent is controlled by the relative amounts of epoxy and active hydrogen present. Preferably, the mixing ratio of binder to curing agent is from 1:1 to 10:1, more preferably from 5:1 to 2:1, by solid volume.
[0246] Based on the total weight of the coating composition, the total amount of the binder (e.g., epoxy-based binder) and the one or more curing agents is preferably 20 to 80 wt %, more preferably 30 to 70 wt %, and still more preferably 40 to 60 wt %. Based on the total weight of the coating composition, the total amount of the one or more curing agents in the coating composition of the present invention is preferably 10 wt % to 40 wt %, and still more preferably 15 wt % to 30 wt %.
[0247] Curing agent for polysiloxane adhesives
[0248] As mentioned above, the polysiloxane-based binder that can exist in the coating composition of the present invention is curable, and contains curing reactive functional groups, such as silanol, methanol, carboxyl, ester, hydride, alkenyl, vinyl ether, allyl ether, alkoxysilane, ketoxime, amine, epoxy group, isocyanate and / or alkoxy group.Preferably, the polysiloxane-based binder contains at least two curing reactive functional groups.Optionally, the polysiloxane-based binder comprises a curing reactive functional group that exceeds one type.Preferably, the polysiloxane-based binder comprises a single type of curing reactive functional group. Suitable crosslinking agent and / or curing agent are selected according to the curing reactive functional group present in the polysiloxane-based binder.
[0249] In preferred polysiloxane-based binders, the curing reactive functional groups are silanols, carbinols, alkoxysilanes, isocyanates, amines and / or epoxy groups. In still more preferred polysiloxane-based binders, the curing reactive functional groups are silanols, amines and / or alkoxysilanes.
[0250] It may be necessary to add a crosslinking agent to obtain the desired crosslinking density. If the curing reactive functional group is a silanol, the preferred crosslinking agent is an organosilicon compound represented by the general formula shown below, a partial hydrolysis condensation product thereof, or a mixture of two or more such compounds:
[0251] R d -Si-K 4-d
[0252] in,
[0253] Each R is independently selected from an unsubstituted or substituted monovalent hydrocarbon group having 1 to 6 carbon atoms or a C substituted by a poly(alkylene oxide) 1-6 alkyl;
[0254] Each K is independently selected from a hydrolyzable group, such as an alkoxy group; and d is 0, 1 or 2, more preferably 0 or 1.
[0255] Preferred crosslinking agents of this type include tetraethoxysilane, vinyltri(methylethyloxime)silane, methyltri(methylethyloxime)silane, vinyltrimethoxysilane, methyltrimethoxysilane and vinyltriisopropenoxysilane, and hydrolysis condensation products thereof.
[0256] If the cure-reactive functional groups are dialkoxy or trialkoxy groups, a separate crosslinker is generally not required.
[0257] The crosslinker is preferably present in an amount of 0-10 wt. %, based on the total dry weight of the coating composition. Suitable crosslinkers are commercially available, such as Silcate TES-40WN from Wacker and Dynasylan A from Evonik.
[0258] If the curing reactive functional group is an amine, epoxy or isocyanate, the curing agent is preferably amine, sulfur or epoxy functional.
[0259] The curing agent may also be a dual curing agent, for example, containing both amine / sulfur / epoxy / isocyanate and alkoxysilane. A preferred dual curing agent is represented by the following general formula:
[0260]
[0261] in
[0262] LL is independently selected from unsubstituted or substituted monovalent hydrocarbon groups having 1 to 6 carbon atoms;
[0263] Each M is independently selected from a hydrolyzable group, such as an alkoxy group;
[0264] a is 0, 1 or 2, preferably 0 or 1;
[0265] b is an integer from 1 to 6; and
[0266] Fn is an amine, epoxy, glycidyl ether, isocyanate or thio group.
[0267] Preferred examples of such dual curing agents include 3-isocyanate propyl trimethoxy silane, 3-isocyanate propyl triethoxy silane, 3-aminopropyl trimethoxy silane, 3-aminopropyl triethoxy silane, (3-glycidoxypropyl) trimethoxy silane, 3-mercaptopropyl trimethoxy silane. A particularly preferred curing agent is 3-aminopropyl triethoxy silane, such as Dynasylan AMEO from Evonik.
[0268] This dual curing agent can be used as a separate curing agent or for end-capping polysiloxane-based adhesives, so that before the curing reaction, the end groups of polysiloxane-based adhesives are modified. For example, the mixing of polysiloxane-based adhesives and curing agents can be carried out shortly before the coating is applied to the product, for example, one hour before the coating or a shorter time is carried out, or the polysiloxane-based adhesive can be supplied with a curable form, but keeps dry to prevent premature curing. In some compositions, curing agent / end-capping agent is preferably supplied to the remainder of the coating composition separately to prevent curing before the coating is applied to the object.
[0269] Curing agent for polyurethane and polyurea adhesives
[0270] Catalysts are optionally used with polyurethane and polyurea binders to accelerate the curing reaction. Examples of suitable catalysts include: tetramethylbutylene diamine (TMBDA), N-alkylmorpholine, triethylamine (TEA), 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), pentamethyldiethylene-triamine (PMDETA), zinc octoate, dioctyltin dilaurate dibutyltin dilaurate and dibutyltin oxide, particularly selected from dioctyltin dilaurate dibutyltin dilaurate and dibutyltin oxide.
[0271] Accelerator
[0272] Coating composition of the present invention optionally also comprises curing accelerator.In some preferred coating compositions, there is no curing accelerator.In such composition, curing agent is adopted and independent catalyst is not used to accelerate crosslinking process.In other preferred coating compositions, curing accelerator is adopted to accelerate the speed of curing reaction to form coating, for example film coating.
[0273] Any conventional curing accelerator may be present in the coating composition of the present invention. For example, the curing accelerator may be selected from imidazoles, anhydrides, polyamides, aliphatic amines, epoxy resin-amine adducts, phenols and tertiary amines. Imidazoles such as 2-methylimidazole are preferred curing accelerators.
[0274] The total amount of curing accelerator present in the coating composition of the present invention is preferably 0-5 wt%, more preferably 0.1-2 wt%, and still more preferably 0.1-1 wt%, based on the total weight of the coating composition.
[0275] Accelerator for epoxy adhesives
[0276] When the binder is epoxy-based (eg, epoxy resin binder), the curing accelerator may be any known curing accelerator for epoxy-based coating systems. Examples include tertiary amines, (meth)acrylates, imidazoles, organic acids, phenols, and organic phosphines.
[0277] Examples of suitable tertiary amines are triethanolamine, dialkylaminoethanol, triethylenediamine, 1,4-diazabicyclo[2.2.2]octane, 1,8-diaza-bicyclo[5.4.0]undec-7-ene and 2,4,6-tris(dimethylaminomethyl)phenol. A particularly preferred accelerator is 2,4,6-tris(dimethylaminomethyl)phenol, such as Ancamine K54 from Evonik.
[0278] Examples of suitable imidazoles are 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole and 2-heptadecylimidazole.
[0279] Examples of suitable organic acids are benzoic acid derivatives, such as salicylic acid.
[0280] Examples of suitable organic phosphines are tributylphosphine, methyldiphenylphosphine, triphenylphosphine, diphenylphosphine and phenylphosphine.
[0281] Examples of suitable phenols are alkylphenols such as nonylphenol and Novares LS500.
[0282] A particularly preferred curing accelerator, in particular for epoxy adhesives, is a (meth)acrylate. The (meth)acrylate accelerator is preferably an aliphatic (meth)acrylate containing at least two (meth)acrylate functional groups connected by an organic linker. Such a polyester can be a diester, triester or tetraester.
[0283] The molecular weight of the (meth)acrylate is preferably less than 1,000.
[0284] Preferably, the (meth)acrylate is a (meth)acrylate of a polyol (such as a diol or triol or a sugar polyol such as a sugar alcohol). It is not necessary that all OH groups in the polyol carry a (meth)acrylate group, but preferably there should be at least two ester functional groups in the (meth)acrylate. Suitable polyols for functionalization include alkylene glycols (e.g., hexylene glycol, pentylene glycol), sugars (e.g., monosaccharides or disaccharides) or polyols (especially sugar alcohols), such as erythritol, sorbitol, maltitol and mannitol.
[0285] Particularly preferred (meth)acrylates used as curing accelerators have the formula (I)
[0286]
[0287] in
[0288] Each R is H or Me;
[0289] Each n is 2-5;
[0290] And L represents a residue of a polyol, a sugar or a sugar alcohol, wherein at least two OH groups carried by the polyol are derivatized as shown in formula (I).
[0291] Preferably, L consists only of C, H and O atoms. Preferably, L has a molecular weight of less than 1000 g / mol.
[0292] Examples of commercially available (meth)acrylates include M-Cure 400 from Sartomer.
[0293] Accelerator for polysiloxane adhesives
[0294] When the binder is a polysiloxane system, the curing accelerator preferably includes a catalyst. Representative examples of catalysts that can be used include transition metal compounds, metal salts of various metals (such as tin, iron, lead, barium, cobalt, zinc, antimony, cadmium, manganese, chromium, nickel, aluminum, gallium, germanium, titanium, boron, lithium, potassium, bismuth and zirconium) and organic metal complexes. The salt is preferably a salt of a long-chain carboxylic acid and / or a chelate or an organic metal salt.
[0295] Examples of suitable tin catalysts include, for example, dibutyltin dilaurate, dibutyltin dioctoate, dibutyltin diacetate, or dioctyltin dilaurate. Examples of commercially available tin catalysts include BNT-CAT 400 and BNT-CAT 500 from BNT Chemicals, FASCAT 4202 from PMC Organometallix, and Metatin Katalysator 702 from DOW.
[0296] Examples of suitable zinc catalysts are zinc 2-ethylhexanoate, zinc naphthenate and zinc stearate.Examples of commercially available zinc catalysts include K-KAT XK-672 and K-KAT670 from King Industries, and Borchi Kat 22 from Borchers.
[0297] Examples of suitable bismuth catalysts are organic bismuth compounds such as bismuth 2-ethylhexanoate, bismuth octoate and bismuth neodecanoate. Examples of commercial organic bismuth catalysts are Borchi Kat 24 and Borchi Kat 315 from Borchers, K-KAT XK-651 from King Industries, Reaxis C739E50 from Reaxis, and TIB KAT716 from TIB Chemicals.
[0298] Examples of suitable titanium catalysts are organic titanium catalysts such as titanium naphthenate, tetrabutyl titanate, tetra(2-ethylhexyl) titanate, triethanolamine titanate, tetra(isopropenyloxy) titanate, titanium tetrabutoxide, titanium tetrapropoxide, titanium tetraisopropoxide and chelated titanates such as diisopropyl bis(acetylacetonato) titanate, diisopropyl bis(ethylacetylacetonato) titanate and diisopropyl bis(ethylacetylacetonato) titanium. Examples of suitable commercially available titanium catalysts are Tyzor IBAY from Dorf Ketal and TIB KAT 517 from TIB Chemicals.
[0299] Other suitable catalysts are iron catalysts such as iron stearate and iron 2-ethylhexanoate, lead catalysts such as lead octoate and lead 2-ethyloctoate, cobalt catalysts such as cobalt 2-ethylhexanoate and cobalt naphthenate, manganese catalysts such as manganese 2-ethylhexanoate, and zirconium catalysts such as zirconium naphthenate, tetrabutyl zirconate, tetra(2-ethylhexyl) zirconate, triethanolamine zirconate, tetra(isopropenyloxy) zirconate, zirconium tetrabutoxide, zirconium tetrapropoxide and zirconium tetraisopropoxide.
[0300] Other suitable catalysts are zirconates.
[0301] The catalyst may also be an organic compound such as triethylamine, guanidine, amidine, cyclic amine, tetramethylethylenediamine, 1,4-ethylenepiperazine and pentamethyldiethylenetriamine. Other examples include aminosilanes such as 3-aminopropyltriethoxysilane and N,N-dibutylaminomethyl-triethoxysilane.
[0302] In a preferred embodiment, the catalyst is a tin, titanium, bismuth, guanidine and / or amidine catalyst, more preferably a titanium, guanidine and / or amidine catalyst.
[0303] Preferably, the catalyst is present in the coating composition of the present invention in an amount of 0.01 to 5 wt%, more preferably 0.05 to 4 wt%, based on the total dry weight of the coating composition.
[0304] Reactive diluent
[0305] The coating composition of the present invention preferably further comprises a reactive diluent. The reactive diluent may be used alone or in combination, for example, in the form of a mixture of two or more reactive diluents.
[0306] Preferably, the viscosity of the reactive diluent is <100 cP, preferably <50 cP, more preferably <30 cP, and still more preferably <20 cP.
[0307] Preferably, the reactive diluent has an epoxy equivalent weight (EEW) of 50-500, more preferably 100-400, and still more preferably 100-300.
[0308] Preferred reactive diluents for use in the coating composition of the present invention are formed from modified epoxy compounds. Examples of suitable reactive diluents include: phenyl glycidyl ether, C 1-16 Alkyl glycidyl ether, neodecanoic acid C 8-10 Alkyl glycidyl ester (ie R 1 R 2 R 3 C-COO-Gly, where R 1 , R 2 and R 3 C 8-10 alkyl, and Gly is glycidyl), olefin epoxide, CH 3 -(CH 2 ) n -Gly (wherein n is 11 to 13 and Gly is a glycidyl group), 1,4-butanediol diglycidyl ether (i.e., Gly-O-(CH 2 ) 4 -O-Gly), 1,6-hexanediol diglycidyl ether (i.e. Gly-O-(CH 2 ) 6 -O-Gly), neopentyl glycol diglycidyl ether (i.e. Gly-O-CH 2 -C(CH 3 ) 2 -CH 2 -O-Gly), trimethylolpropane triglycidyl ether (CH 3 -CH 2 -C(CH 2 -O-Gly) 3 ), C 1-20 -alkylphenyl glycidyl ether (preferably, C 1-5 Alkylphenyl glycidyl ethers, such as methylphenyl glycidyl ether, ethylphenyl glycidyl ether, propylphenyl glycidyl ether and p-tert-butylphenyl glycidyl ether (p-TBPGE), and the reaction product of epichlorohydrin with oil obtained from cashew nut shell.
[0309] Particularly preferred reactive diluents are C 1-16 Alkyl glycidyl ether, and more preferably C 10-14 Alkyl glycidyl ether.
[0310] Another preferred reactive diluent is the reaction product of epichlorohydrin and oil obtained from cashew nut shells.An example of a commercially available reactive diluent of this type is Cardolite NC-513 from Cardolite.
[0311] Another preferred class of reactive diluents is aliphatic reactive diluents. Aliphatic reactive diluents are preferably formed by the reaction of a compound containing at least one aliphatic epoxy functionality with an aliphatic alcohol or polyol (such as 1,6-hexanediol diglycidyl ether or 1,4-butanediol diglycidyl ether). Aliphatic glycidyl ethers with chain lengths of 8 to 14 are also preferred. Aliphatic reactive diluents can contribute to the flexibility of the coating film.
[0312] Based on the total weight of the coating composition, the coating composition of the present invention preferably comprises 0-30 wt%, more preferably 10-25 wt%, and still more preferably 10-20 wt% of a reactive diluent. The presence of a reactive diluent in the coating composition of the present invention reduces the viscosity of the coating composition and facilitates the preparation of a high solid, solvent-free coating composition.
[0313] Based on the total weight of the coating composition, the total amount of binder (e.g., epoxy-based binder), one or more curing agents, accelerators, and reactive diluents is preferably 20 to 80 wt%, more preferably 30 to 70 wt%, and still more preferably 40 to 60 wt%.
[0314] Hollow, inorganic, spherical filler particles
[0315] The coating composition of the present invention comprises hollow, inorganic, spherical filler particles. Suitable hollow, inorganic, spherical filler particles are commercially available. Examples of commercially available hollow, inorganic, spherical filler particles include Fillite Cenosphere, Poraver (expanded glass), Thermospheres, Omega balls (available from, for example, 3M, Trelleborg, Potters, SMC minerals) and Hollolite.
[0316] Hollow, inorganic, spherical particles are a key component of the coating composition. These particles contribute to the thermal insulation provided by the coating prepared with the coating composition, as well as the coating's resistance to cracking, even during exposure to high temperatures (e.g., 150°C), thermal shocks (e.g., directly from 150 to -20°C), and thermal cycling between -20 and 60°C.
[0317] The inorganic, spherical filler particles are hollow. This means that the particles have a void or cavity in their center. This void or empty space is filled with a gas, preferably air. This provides thermal insulation of the coating. The preferred inorganic, spherical filler particles for use in the present invention are substantially hollow. Therefore, preferably, the volume of the void or cavity is at least 70% by volume of the total volume of the particle, and more preferably at least 80% by volume. Preferably, the hollow, inorganic, spherical filler particles have a density as low as practical, for example, the density of the hollow, inorganic, spherical filler particles can be 0.1-1 g / cm -3 , more preferably 0.2-0.8gcm -3 , and still more preferably 0.25-0.5 gcm -3 , for example, as specified in the technical specifications provided by the supplier. This reflects the fact that the particles are hollow rather than solid. Lower density particles are advantageous because they have thinner walls, which in turn improves thermal insulation.
[0318] Preferably, the hollow, inorganic, spherical filler particles present in the coating composition of the present invention have a crush strength of at least 3000 psi, as measured, for example, by a Nitrogen Isostatic Crush Strength test. This is beneficial because it means that the filler particles are not crushed during processing, thereby maintaining their ability to provide thermal insulation in the final coating. It is also advantageous that the filler particles do not change shape and / or size during processing, so they can be densely packed and achieve a high build in the final coating formed.
[0319] The hollow, inorganic, spherical filler particles present in the coating composition of the present invention include the following and are more preferably composed of the following: glass, ceramic or metal oxide. More preferably, the hollow, inorganic, spherical filler particles present in the coating composition of the present invention include glass, and are still more preferably composed of glass. This is because glass particles provide a good balance between crushing strength, hardness and the conductivity. Optionally, the hollow, inorganic, spherical filler particles present in the coating composition of the present invention can be surface treated. Some examples of surface treatment include the hydrophobicity for changing the surface, for improving the compatibility with the binding agent and / or for promoting the processing of the chemicals in the binding agent.
[0320] The hollow, inorganic filler particles present in the coating composition of the present invention are generally spherical, and more preferably spherical. This is advantageous because it enables the filler particles to be packed more tightly together in the coating composition of the present invention. Preferably, the Z-average diameter of the hollow, inorganic filler particles is 1 to 100 μm, more preferably 1 to 80 μm, and still more preferably 10-50 μm, as determined using a Malvern Mastersizer 2000 according to ISO 22412:2017. These particle sizes are preferred to ensure that the coating has sufficient thermal insulation and to achieve high filling efficiency in the coating.
[0321] Preferred coating compositions of the present invention comprise 30-60 volume %, more preferably 30-55 volume %, and still more preferably 40-55 volume % of hollow, inorganic, spherical filler particles, based on the total volume of the composition.
[0322] Preferred coating compositions of the present invention comprise 10-40 wt%, more preferably 15-35 wt%, and still more preferably 20-30 wt% of hollow, inorganic, spherical filler particles, based on the total weight of the composition.
[0323] Hollow, organic, spherical filler particles
[0324] Coating composition of the present invention comprises hollow, organic, spherical filler particles. Hollow, organic, spherical filler particles present in coating composition of the present invention can be prepared by conventional polymerization process such as emulsion polymerization, seed crystal growth polymerization and suspension polymerization. Polymerization can be a single stage process or a multi-step process. Alternatively, suitable hollow, organic, spherical filler particles are commercially available. Examples of commercially available hollow, organic, spherical filler particles include Dualite (from Chase), Sunsheres (from Dow) and Expancel (from Nouryon).
[0325] Hollow, organic, spherical particles are a key component of the coating composition. These particles contribute to the thermal insulation provided by the coating prepared using the coating composition, as well as the crack resistance and adhesion, i.e., peel resistance, of the coating.
[0326] The organic, spherical filler particles are hollow. This means that the particles have a void or cavity in their center. This void or empty space can be filled with a gas, preferably air, C 1-8Alkanes or mixtures thereof are filled. This provides thermal insulation to the coating. Preferred organic, spherical filler particles for use in the present invention are substantially hollow. Thus, preferably, the volume of the voids or cavities is at least 70% by volume of the total volume of the particles, and more preferably at least 80% by volume. Preferably, the hollow, organic, spherical filler particles have a density as low as practically possible, for example, the density of the hollow, organic, spherical filler particles is 0.005-0.9 g / cm -3 , more preferably 0.01-0.5gcm -3 , still more preferably 0.015-0.2 gcm -3 , for example, as specified in the technical specifications provided by the supplier. This reflects the fact that the particles are hollow rather than solid.
[0327] The hollow, organic, spherical filler particles present in the coating composition of the present invention include and more preferably consist of poly(meth)acrylates, polystyrenes, polyacrylamides, polyurethanes, polysiloxanes, polyolefins (e.g., polyethylene, polypropylene, polytetrafluoroethylene), polyacrylonitrile, nylons, poly(vinyl esters), vinylidene, polyacetates, poly(esters) or copolymers thereof. It has been found that hollow, organic, spherical filler particles comprising these polymers produce coatings with high thermal insulation and good crack resistance, even at high temperatures.
[0328] The hollow, organic filler particles present in the coating composition of the present invention are generally spherical, and more preferably spherical. This is advantageous because it enables the filler particles to be packed more closely together in the coating composition of the present invention. Preferably, the Z-average diameter of the hollow, organic filler particles is 10 to 150 μm, more preferably 10 to 120 μm, and still more preferably 15-120 μm, as measured by ISO 22412:2017 using a Malvern Mastersizer 2000. These particle sizes are preferred to ensure that the coating has sufficient thermal insulation and to achieve high filling efficiency in the coating.
[0329] Preferred coating compositions of the present invention comprise 5-20 volume %, more preferably 10-20 volume % and still more preferably 10-15 volume % of hollow, organic, spherical filler particles, based on the total volume of the composition.
[0330] Preferred coating compositions of the present invention comprise 0.25-1.75 wt. %, more preferably 0.25-1 wt. %, and still more preferably 0.3-0.7 wt. % of hollow, organic, spherical filler particles, based on the total weight of the composition.
[0331] In the preferred coating composition of the present invention, the average diameter of the hollow, organic, spherical filler particles is greater than the average diameter of the hollow, inorganic, spherical filler particles. Preferably, the average diameter of the hollow, organic, spherical filler particles is 1-5 times, and more preferably 2-4 times, the average diameter of the hollow, inorganic, spherical filler particles. It has been found that with this combination of hollow filler particles, a coating having a high level of thermal insulation as well as peeling resistance and cracking resistance can be provided.
[0332] In the preferred coating composition of the present invention, the volume ratio of hollow, inorganic, spherical filler particles to hollow, organic, spherical particles is 1.1:1.0 to 10.0:1.0, preferably 5.1:1.0 to 1.2:1.0, more preferably 4.1:1.0 to 1.2:1.0, and still more preferably 3.8:1.0 to 1.3:1.0. It has been found that with this ratio (where the volume amount of hollow, inorganic, spherical filler particles is greater than the volume amount of hollow, organic, spherical filler particles), the most ideal balance of crack resistance and peel resistance is provided while maintaining sufficient thermal insulation and hardness.
[0333] In further preferred coating compositions of the present invention, the weight ratio of hollow, inorganic, spherical filler particles to hollow, organic, spherical particles is at least 50:2.5, preferably from 50:2.5 to 50:0.25.
[0334] Based on the total volume of the composition, the preferred coating composition of the present invention comprises a total amount of 50-80 volume %, more preferably 60-70 volume % of hollow, inorganic, spherical filler particles and hollow, organic, spherical filler particles. Therefore, the hollow, spherical filler particles account for a significant total volume of the composition and provide its key thermal insulation.
[0335] Additionally, preferred coating compositions of the present invention comprise a total amount of 10-40 wt %, more preferably 15-30 wt %, of hollow, inorganic, spherical filler particles and hollow, organic, spherical filler particles, based on the total weight of the composition.
[0336] Thickener
[0337] The coating composition of the present invention further comprises a thickener. Optionally, a mixture of at least 2 or 3 thickeners may be present. The presence of a thickener in the coating composition of the present invention advantageously improves storage stability, coating properties of the composition and anti-sagging properties of the composition.
[0338] Therefore, another coating composition of the present invention comprises:
[0339] (i) a binder;
[0340] (ii) a curing agent;
[0341] (iii) hollow, inorganic, spherical filler particles;
[0342] (iv) hollow, organic, spherical filler particles; and
[0343] (v) Thickeners.
[0344] Preferred coating compositions of the present invention contain a solvent-free thickener. This is beneficial in reducing the VOC content of the composition and increasing its solids content.
[0345] Various conventional thickeners can be used in the coating composition of the present invention. For example, fumed silica can be used as a thickener. However, the preferred coating composition of the present invention comprises an oligomeric thickener. Without wishing to be bound by theory, it is believed that these thickeners gradually increase the viscosity at low shear rates by establishing an interactive network of crystalline fibers, thereby improving the anti-sagging property of the composition. This is particularly beneficial when the coating composition of the present invention is applied to a non-horizontal, such as a vertical surface. Optionally, the coating composition of the present invention comprises fumed silica and at least one (e.g., one) oligomeric thickener.
[0346] Examples of suitable oligomeric thickeners include polyhydroxycarboxylic acid amides, polyhydroxycarboxylates, modified ureas, metal sulfonates, acrylated oligoamines, polyacrylic acids, modified urethanes, micronized amide waxes, micronized amide-modified castor oil waxes, micronized waxes derived from castor oil, preactivated amide waxes dispersed in (meth)acrylate monomers, or polyamides. Preferred coating compositions of the present invention comprise an oligomeric thickener selected from the group consisting of micronized amide waxes, micronized amide-modified castor oil waxes, micronized waxes derived from castor oil, preactivated amide waxes in (meth)acrylate monomers. A particularly preferred thickener is an amide wax.
[0347] Oligomeric thickeners for use in the coating composition of the present invention are commercially available. For example, micronized amide waxes are available under the trade name Crayvallac (from Arkema).
[0348] The amount of thickener, preferably oligomeric thickener, present in the coating composition of the present invention is preferably 0 to 5 wt %, more preferably 0.25-3.0 wt %, and still more preferably 0.5-3.0 wt %, and still more preferably 0.5 to 2.0 wt %, based on the total weight of the coating composition.
[0349] Adhesion promoter
[0350] The coating composition of the present invention preferably further comprises an adhesion promoter, more preferably an organosilane adhesion promoter. Such adhesion promoters are well known in the art.
[0351] Silanes, especially organosilanes, are believed to improve the drying properties of coating compositions, especially at low temperatures. They are also believed to improve flexibility, adhesion to substrates, and corrosion resistance.
[0352] Preferably, the silane comprises epoxy groups.Preferably, the Mw of the silane is less than 400 g / mol.
[0353] Preferred silanes for use in the coating compositions of the present invention have the general formula (II) or (III):
[0354] (II) YR (4-z) SiX z
[0355] (III)YR (3-y) R 1 SiX y
[0356] in
[0357] z is an integer from 1 to 3;
[0358] y is an integer from 1 to 2;
[0359] R is a hydrocarbon radical having 1 to 12 C atoms, which optionally contains an ether or amino linker;
[0360] R 1 is a hydrocarbon group having 1 to 12 C atoms;
[0361] Y is a functional group combined with R that can react with a binder (e.g., an epoxy-based binder) and / or a curing agent; and
[0362] Each X independently represents a halogen group or an alkoxy group.
[0363] In preferred compounds of formula (II) and (III), Y is an isocyanate, epoxy, amino, hydroxyl, carboxyl, acrylate or methacrylate group. The Y group may be bound to any part of the chain R. It will be appreciated that where Y represents an epoxy group, then R will have at least two carbon atoms to enable the formation of an epoxide ring system.
[0364] In other preferred compounds of formula (II) and (III), Y is an amino group or an epoxy group. The amino group is preferably NH 2 Preferably, Y is an epoxy group. If the Y group is an amino group that can react with an epoxy-based binder, it is preferred that the silane is provided separately from the epoxy-based binder together with the curing agent. Typically, in the kit of the present invention, the silane should not react with any component of the components of the kit in which the silane is present.
[0365] In preferred compounds of formula (II) or (III), R is preferably a hydrocarbon radical having up to 12 carbon atoms. Hydrocarbon radical means a radical containing only C atoms and H atoms. It may include an alkylene chain, or a combination of an alkylene chain and a ring such as a phenyl or cyclohexyl ring. The term "optionally containing an ether or amino linker" implies that the carbon chain may be interrupted by -O- or -NH- groups in the chain, forming, for example, silanes, such as [3-(2,3-epoxypropoxy)propyl]trimethoxysilane: H 2 COCHCH 2 OCH 2 CH 2 CH 2 Si(OCH 3 ) 3 .
[0366] It is preferred that the group Y is not bonded to a carbon atom to which such a linker -O- or -NH- is bonded.
[0367] R is preferably an unsubstituted (obviously with the exception of Y), unbranched alkyl chain having 2 to 8 C atoms.
[0368] In preferred compounds of formula (II) and (III), X is an alkoxy group, such as C 1-6 Alkoxy, particularly preferably methoxy or ethoxy. It is also particularly preferred that two or three alkoxy groups are present. Thus, in compounds of formula (II), z is preferably 2 or 3, especially 3. In compounds of formula (III), y is preferably 2.
[0369] In preferred compounds of formula (III), R 1 Preferably C 1-4 An alkyl group, such as a methyl group.
[0370] One particularly preferred silane present in the coating composition of the present invention has the formula (IV):
[0371] (IV)Y'-R'( 4-z' )SiX' z’
[0372] in
[0373] z' is an integer from 2 to 3;
[0374] R' is an unsubstituted, unbranched alkyl radical having 2 to 8 C atoms, which optionally contains an ether or amino linker;
[0375] Y' is an amino or epoxy functional group bonded to the R' group; and
[0376] X' represents an alkoxy group.
[0377] Examples of silanes suitable for use in the coating compositions of the present invention include: Products sold by D, manufactured by OSi Specialties Silane, and manufactured by Wacker Silane.
[0378] Specific examples include: methacryloxypropyl trimethoxysilane (Dynasylan MEMO, Silquest A-174NT), 3-mercaptopropyl trimethoxy / ethoxy silane (Dynasylan MTMO or 3201; Silquest A-189), 3-glycidoxypropyl trimethoxy silane (Dynasylan GLYMO, Silquest A-187), tris(3-trimethoxysilylpropyl) isocyanurate (Silquest Y-11597), γ-mercaptopropyl trimethoxy silane (Silquest A-189), β-(3,4-epoxycyclohexyl)ethyl trimethoxy silane (Silquest A-186), γ-isocyanatopropyl trimethoxy silane (Silquest A-Link 35, Genosil GF40), (methacryloyloxymethyl) trimethoxy silane (Genosil XL 33), isocyanatomethyl) trimethoxy silane (Genosil XL 43), aminopropyltrimethoxysilane (Dynasylan AMMO; Silquest Al 110), aminopropyltriethoxysilane (Dynasylan AMEO) or N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (Dynasylan DAMO, Silquest Al 120) or N-(2-aminoethyl)-3-aminopropyltriethoxysilane, triaminofunctional trimethoxysilane (Silquest A-1130), bis(γ-trimethoxysilylpropyl)amine (Silquest Al 170), N-ethyl-γ-aminoisobutyl(isobytyl)trimethoxysilane (Silquest A-Link 15), N-phenyl-γ-aminopropyltrimethoxysilane (Silquest Y-9669), 4-amino-3,3-dimethylbutyltrimethoxysilane (Silquest Yl 1637), (N-cyclohexylaminomethyl)triethoxysilane (Genosil XL 926), (N-phenylaminomethyl)trimethoxysilane (Genosil XL 973), Deolink Epoxy TE and Deolink Amino TE (DOG Deutsche Oelfabrik) and mixtures thereof.
[0379] Other preferred silanes include 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-(aminoethyl)-aminopropyltrimethoxysilane (H 2 NCH 2 CH 2 NHCH 2 CH2 CH 2 Si(OCH 3 ) 3 ), 3-aminopropylmethyldiethoxysilane, 3-(2-aminoethylamino)propylmethyldimethoxysilane (H 2 NCH 2 CH 2 NHCH 2 CH 2 CH 2 SiC 3 (OCH 3 ) 2 ), [3-(2,3-epoxypropoxy)propyl]triethoxy-silane (H 2 COCHCH 2 OCH 2 CH 2 CH 2 Si(OCH 2 CH 3 ) 3 、[3-(2,3-epoxypropoxy)propyl]trimethoxysilane(H 2 COCHCH 2 OCH 2 CH 2 CH 2 Si(OCH 3 ) 3 ).
[0380] 3-Glycidyloxypropyltrimethoxysilane is particularly preferred. Mixtures of silanes may also be used.
[0381] The amount of adhesion promoter, preferably organosilane adhesion promoter, present in the coating composition of the present invention is preferably 0 to 15 wt %, more preferably 0.1-10 wt %, and still more preferably 0.5-5 wt %, and still more preferably 0.5 to 3 wt %, based on the total weight of the coating composition. In the preferred composition of the present invention, the total amount of organosilane present therein is preferably 0 to 15 wt %, more preferably 0.1-10 wt %, and still more preferably 0.5-5 wt %, and still more preferably 0.5 to 3 wt %, based on the total weight of the coating composition.
[0382] additive
[0383] The coating composition of the present invention optionally contains various additives. Examples of additives optionally present in the composition of the present invention include co-binders, hydrocarbon resins, anti-settling agents, fillers, amino alcohols, coloring pigments, drying agents, dispersants and surface modifiers. Examples of compounds that are preferably absent (e.g., present at less than 0.1 wt %, preferably less than 0.05 wt %) in the composition include alkaline earth metal hydroxides, aluminum group hydroxides and phosphorus-containing compounds.
[0384] The further additives are preferably present in an amount of 0 to 20% by weight, more preferably 0.1-10% by weight, still more preferably 0.1 to 5% by weight and particularly preferably 0.5 to 5% by weight, based on the total weight of the coating composition.
[0385] The coating composition of the present invention optionally comprises a co-binder. Examples of suitable co-binders include: saturated polyester resins, polyvinyl acetate, polyvinyl butyrate, copolymers of vinyl acetate, vinyl isobutyl ether, copolymers of vinyl chloride and vinyl isobutyl ether, styrene copolymers such as styrene / butadiene copolymers, acrylic resins, hydroxy-acrylate copolymers, fatty acids and cyclized rubbers.
[0386] The coating composition of the present invention preferably comprises 0 to 10 wt % of a co-binder, based on the total weight of the composition.
[0387] The coating composition of the present invention optionally comprises a hydrocarbon resin. Various hydrocarbon resins are suitable for inclusion in the coating composition. Preferably, the hydrocarbon resin is a petroleum resin.
[0388] Examples of petroleum resins suitable for the present invention include: 9 Aromatic petroleum resin obtained by polymerization of a styrene derivative such as α-methylstyrene, o-, m-, p-cresol, indene, methylindene, cumene, naphthalene or vinyltoluene, wherein the C 9 The fraction is obtained from heavy oil produced as a by-product of naphtha cracking; 5 Aliphatic petroleum resins obtained by polymerizing fractions such as 1,3-pentadiene or isoprene, 2-methyl-2-butene, cyclopentadiene, dicyclopentadiene or cyclopentene. 9 Fractions and C 5 The copolymer obtained by fraction polymerization is a petroleum resin, wherein C 5 Aliphatic petroleum resins obtained by ring-polymerizing a portion of conjugated dienes such as cyclopentadiene or 1,3-pentadiene, resins obtained by hydrogenating the aromatic petroleum resins, and alicyclic petroleum resins obtained by polymerizing dicyclopentadiene. 9The mixture is reacted under catalytic conditions to obtain a mixture of diaryl compounds and triaryl compounds.
[0389] The coating composition of the present invention preferably comprises 0 to 10 wt. % of a hydrocarbon resin, based on the total weight of the composition.
[0390] Composition
[0391] Preferred coating compositions of the present invention comprise:
[0392] (i) an adhesive, preferably an epoxy-based adhesive;
[0393] (ii) a curing agent;
[0394] (iii) hollow, inorganic (e.g. glass), spherical filler particles; and
[0395] (iv) hollow, organic, spherical filler particles;
[0396] The volume ratio of the inorganic, spherical filler particles to the organic, spherical filler particles is at least 1.1:1.
[0397] Another preferred coating composition of the present invention comprises:
[0398] (i) Epoxy adhesive;
[0399] (ii) a curing agent;
[0400] (iii) accelerator;
[0401] (iv) reactive diluents;
[0402] (v) hollow, inorganic, spherical filler particles, preferably hollow, glass, spherical filler particles;
[0403] (vi) hollow, organic, spherical filler particles;
[0404] (vii) optionally an adhesion promoter; and
[0405] (viii) optionally a thickener;
[0406] The volume ratio of the inorganic, spherical filler particles to the organic, spherical filler particles is at least 1.1:1.
[0407] Another preferred coating composition of the present invention comprises:
[0408] (i) 15-50 wt %, preferably 20-40 wt % of an epoxy adhesive;
[0409] (ii) 10-40 wt %, preferably 15-30 wt % of a curing agent;
[0410] (iii) 15-35 wt %, preferably 20-30 wt %, of hollow, inorganic (eg glass), spherical filler particles; and
[0411] (iv) 0.25-1.0 wt %, preferably 0.3-0.7 wt % of hollow, organic, spherical filler particles;
[0412] The volume ratio of the inorganic, spherical filler particles to the organic, spherical filler particles is at least 1.1:1.
[0413] Particularly preferred coating compositions of the present invention comprise:
[0414] (i) 15-50 wt %, preferably 20-40 wt % of an epoxy adhesive;
[0415] (ii) 10-40 wt %, preferably 15-30 wt % of a curing agent;
[0416] (iii) 15-35 wt %, preferably 20-30 wt %, of hollow, inorganic (e.g. glass), spherical filler particles;
[0417] (iv) 0.25-1.0 wt %, preferably 0.3-0.7 wt % of hollow, organic, spherical filler particles;
[0418] (v) 0.1-10 wt %, preferably 0.5-5 wt % of an adhesion promoter; and
[0419] (vi) 0.25-3 wt %, preferably 0.5-2 wt % of a thickener.
[0420] In such a composition, the volume ratio of inorganic, spherical filler particles to organic, spherical filler particles is preferably at least 1.1:1.
[0421] Preferred coating compositions of the present invention have a solids content of at least 98 wt %, more preferably at least 99 wt %. Particularly preferably, the coating composition of the present invention has a solids content of 100 wt %. This means that the coating composition is substantially free of VOCs.
[0422] Preferred coating compositions of the present invention are sprayable. Particularly preferably, the coating compositions of the present invention are thixotropic. Thus, the coating composition flows when shear is applied in a spraying device, but does not flow once applied to a surface. This minimizes the amount of sagging that occurs, even when applying a thick layer of the coating composition.
[0423] Preferred coating compositions of the present invention provide coatings having a thermal conductivity of less than 0.15 W / mK and more preferably in the range of 0 to 0.12 W / mK.
[0424] Preferred coating compositions of the present invention provide coatings having a heat reduction of at least 5°C / mm, and more preferably at least 7°C / mm, more preferably above 9°C / mm.
[0425] Preferred coating compositions of the invention provide coatings that are curable at ambient temperature. Particularly preferred coating compositions provide coatings that are curable at temperatures below 100°C, more preferably below 50°C and still more preferably below 40°C (all at 50% RH). Preferably, the coating composition provides a coating that has a relatively wide temperature range over which the coating is curable, e.g., spanning a range of at least 80°C, more preferably spanning a range of at least 100°C (e.g., 80-150°C).
[0426] Preferred coating compositions of the invention provide coatings having a sag resistance of at least 1.5 mm, more preferably at least 2 mm and more preferably at least 2.5 mm, as determined, for example, by the method described in the Examples. Particularly preferred coating compositions provide coatings having a sag resistance of at least 5 mm and more preferably at least 10 mm.
[0427] Preferred coating compositions of the invention provide coatings which are peel resistant at 150°C when the DFT is at least 5 mm, preferably at least 10 mm.
[0428] When the DFT is at least 5 mm, preferably at least 10 mm, preferred coating compositions of the invention provide coatings having crack resistance during a temperature change from -20°C to 60°C, for example as determined by the method described in the Examples.
[0429] Particularly preferred coating compositions of the present invention provide coatings having one or more of the following:
[0430] A thermal conductivity of less than 0.15 W / mK, more preferably 0-0.12 W / mK;
[0431] a heat reduction of at least 5°C / mm, more preferably at least 7°C / mm;
[0432] Curable at a temperature below 100°C and preferably below 50°C at 50% RH;
[0433] A sag resistance of at least 1.5 mm, more preferably at least 2.0 mm, as determined, for example, by the method described in the Examples;
[0434] Peel resistance at 150°C at a dry thickness of at least 5 mm, preferably at least 10 mm; and / or
[0435] Crack resistance during a temperature change from -20°C to 60°C at a dry thickness of at least 5 mm, preferably at least 10 mm (the crack resistance being determined, for example, by the method described in the examples).
[0436] Containers and kits
[0437] The present invention also relates to a container containing a coating composition as described above. Suitable containers include cardboard boxes lined with a plastic bag and multiple plastic bags (so-called "big bags").
[0438] Alternatively, the coating composition of the present invention can be provided in the form of a kit. In the kit, the curing agent is preferably present in a different container from the binder. Therefore, the kit includes:
[0439] (iii) a first container comprising a binder, optionally hollow, inorganic, spherical filler particles, and optionally hollow, organic, spherical filler particles;
[0440] (iv) a second container containing a curing agent, optionally hollow, inorganic, spherical filler particles, and optionally hollow, organic, spherical filler particles,
[0441] wherein the hollow, inorganic, spherical filler particles and the hollow, organic, spherical filler particles are each present in at least one of the containers, and wherein the volume ratio of the inorganic, spherical filler particles to the organic, spherical filler particles is at least 1.1:1.
[0442] In a preferred kit of the present invention, the hollow, inorganic, spherical filler particles are present in one container (e.g., a first container), and the hollow, organic, spherical filler particles are present in a different container (e.g., a second container). Alternatively, the hollow, inorganic, spherical filler particles and the hollow, organic, spherical filler particles may be present in both the first container and the second container. The preferred kit also comprises a promoter, particularly preferably in the second container. The preferred kit also comprises a reactive diluent, particularly preferably in the first container. The preferred kit also comprises an adhesion promoter, particularly preferably in the first container.
[0443] Particularly preferred kits of the present invention also include a thickener. The thickener may be present in the first container, the second container or both containers. In particularly preferred kits, the thickener is present in both containers.
[0444] manufacture
[0445] The present invention also relates to a method for preparing the coating composition as described above, the method comprising mixing:
[0446] Binder;
[0447] Optional curing agent;
[0448] Hollow, inorganic, spherical filler particles; and
[0449] Hollow, organic, spherical filler particles.
[0450] In a preferred method of the present invention, a portion of each of the binder and the hollow, spherical filler particles is premixed, and separately, the remaining portion of each of the curing agent and the hollow, spherical filler particles is premixed. The two resulting mixtures are then combined and mixed.
[0451] When present, the reactive diluent is preferably premixed with the binder.When present, the adhesion promoter is preferably premixed with the binder.When present, the accelerator is preferably premixed with the curing agent.
[0452] When present, the thickener is preferably premixed with each of the binder and the curing agent.
[0453] Any conventional mixing equipment may be used.
[0454] Coating of surfaces
[0455] The present invention also relates to a method for coating a surface, wherein the method comprises:
[0456] (i) applying the composition as described above; and
[0457] (ii) curing the composition to form a coating on the surface.
[0458] Optionally, the surface is pretreated before applying the coating composition of the present invention. Optionally, the surface is coated with one or more primer compositions before applying the coating composition of the present invention. Therefore, the coating composition of the present invention can be a part of a coating system. In a preferred coating system, one or more primers are applied to the surface, and then the coating composition is applied to the primer layer. The example of a suitable primer includes a polyurethane primer and an epoxy primer. Epoxy primers are particularly preferred.
[0459] The temperature of the surface to which the composition is applied is preferably in the range of -10-180°C, more preferably -5-150°C, still more preferably 0-10° and 10 to 50°C. An advantage of the coating compositions of the present invention is that they can be applied to both hot and cold surfaces.
[0460] The coating composition of the present invention can be applied to the substrate by any conventional coating method, such as spraying, roller coating, dipping, etc. Preferably, the coating composition is applied by spraying, and more preferably by airless spraying. Airless spraying can be carried out, for example, using a two-component airless spray pump. It may be necessary to preheat the product to 70° C. and / or a pressure such as 3 to 6 bar. The coating composition can also be applied manually, for example using a trowel.
[0461] Spraying is preferred because it enables large surface areas to be coated in a uniform manner. In addition, spraying can be used to coat non-horizontal surfaces. Preferably, the substrate is a metal, in particular steel. The invention also relates to a coating comprising a coating composition as described above. Optionally, the coating is applied in multiple steps, wherein a first coating layer is applied, dried and cured, and then subsequent coating layers are applied. Preferably, the number of coating steps is minimized. An advantage of the coating composition of the present invention is that it has a high resistance to sag, so that a thicker coating layer can be applied in a single step. Preferably, the coating layer applied in a single step is 0.2-20 mm, more preferably 0.5-10 mm.
[0462] Coating composition of the present invention can be used to form a single layer coating or a multilayer coating (i.e. a coating system). In the case of a multilayer coating, coating composition of the present invention is preferably used to form a second layer above the primer layer on a substrate (e.g. a metal pipe). Preferably, a topcoat is applied. The example of a suitable topcoat layer is a layer comprising a polyurethane resin, an acrylic resin, a silicone resin or a mixture thereof. However, coating composition of the present invention can also be used as a primer layer.
[0463] Curing
[0464] Preferably, the coating of the present invention is cured. Therefore, once the substrate is coated with the coating composition of the present invention, the coating is preferably cured. Preferably, the coating of the present invention is curable at ambient temperature. Preferably, therefore, the coating of the present invention does not require heating to cause curing. This means that the coating of the present invention is curable over a wide temperature range, for example from lower temperatures to higher temperatures (for example on a hot surface). Particularly preferably, the coating of the present invention is cured in a temperature range of -5 to 50° C. without external heating. Preferably, the curing time (i.e. the time for the surface to dry as determined by the thumb test) is 0.5-10 hours, more preferably 1-5 hours.
[0465] Coatings and products
[0466] The present invention also relates to a substrate coated with a coating composition as described above or a coating as described above. The coating composition of the present invention can be applied to any substrate. Representative examples of substrates include metal substrates (steel, galvanized steel, aluminum, copper), glass, ceramics and polymer materials (such as plastics). A preferred substrate is a metal substrate. More preferably, the substrate is carbon steel. The coating of the present invention provides a thermally insulating coating on such a substrate. Therefore, the type of metal substrate preferably coated with the coating of the present invention is those in contact with hot or cold substances. Examples of metal substrates include tanks, line pipes, elbows and pipe fittings, valves, pumps, manifolds, coils and tracers. A particularly preferred substrate is a metal tank or metal pipe, such as a metal tank and pipe for oil and gas recovery. Preferably, the diameter of the metal tank is more than 5m.
[0467] The substrate may be partially or completely coated with the coating composition or coating of the present invention. However, preferably, all substrates are coated with the coating composition or coating of the present invention. In the case of a tank or a pipe, preferably, the outer wall is coated with the coating composition of the present invention.
[0468] Preferably, the total dry thickness of the coating is 2-150 mm, more preferably 5-100 mm, and still more preferably 8-80 mm. Preferably, the coating is thermally insulating. Preferably, the coating will provide thermal insulation on the metal surface in the range of -196–450°C and more preferably -196–250°C. Therefore, a preferred coating of the present invention is on a metal surface, wherein the coating is thermally insulating and has a thickness of at least 2 mm, and the coating comprises:
[0469] (i) a binder;
[0470] (ii) a curing agent;
[0471] (iii) hollow, inorganic, spherical filler particles; and
[0472] (iv) Hollow, organic, spherical filler particles.
[0473] Preferably, the coating is a thermally insulating coating.Preferred binders, curing agents, filler particles and other ingredients present in the coating are as described above.
[0474] Preferred coatings of the present invention have a thermal conductivity of less than 0.15 W / mK, and more preferably in the range of 0-0.12 W / mK.
[0475] Preferred coatings of the present invention have a heat reduction of at least 5°C / mm, more preferably at least 7°C / mm, and still more preferably above 9°C / mm.
[0476] Preferred coatings of the invention are curable at ambient temperature. Particularly preferred coatings are curable at temperatures below 100°C, more preferably below 50°C and still more preferably below 40°C (all at 50% RH). Preferably, the coatings have a broad temperature range over which they are curable, for example spanning a range of at least 80°C, more preferably spanning a range of at least 100°C (e.g. 80-150°C).
[0477] Preferred coatings of the invention have a sag resistance of at least 1.5 mm, more preferably at least 2.0 mm, as determined, for example, by the method described in the Examples.
[0478] Preferred coatings of the invention are peel resistant at 150°C when the DFT is at least 5 mm, preferably at least 10 mm.
[0479] When the DFT is at least 5 mm, preferably at least 10 mm, preferred coatings of the invention have resistance to cracking during a temperature change from -20°C to 60°C, for example as determined by the method described in the Examples.
[0480] Particularly preferred coatings of the present invention have one or more of the following:
[0481] A thermal conductivity of less than 0.15 W / mK, more preferably 0-0.12 W / mK;
[0482] a heat reduction of at least 5°C / mm, more preferably at least 7°C / mm;
[0483] Curable at a temperature below 100°C and preferably below 50°C at 50% RH;
[0484] A sag resistance of at least 1.5 mm, more preferably at least 2.0 mm, as determined, for example, by the method described in the Examples;
[0485] Peel resistance at 150°C at a dry thickness of at least 5 mm, preferably at least 10 mm; and / or
[0486] Crack resistance during a temperature change from -20°C to 60°C at a dry thickness of at least 5 mm, preferably at least 10 mm (the crack resistance being determined, for example, by the method described in the examples).
[0487] From another aspect, the present invention provides a coating having one or more of the following:
[0488] A thermal conductivity of less than 0.15 W / mK, more preferably 0-0.12 W / mK;
[0489] a heat reduction of at least 5°C / mm, more preferably at least 7°C / mm;
[0490] Curable at a temperature below 100°C and preferably below 50°C at 50% RH;
[0491] A sag resistance of at least 1.5 mm, more preferably at least 2.0 mm, as determined, for example, by the method described in the Examples;
[0492] Peel resistance at 150°C at a dry thickness of at least 5 mm, preferably at least 10 mm; and / or
[0493] Crack resistance during a temperature change from -20°C to 60°C at a dry thickness of at least 5 mm, preferably at least 10 mm (the crack resistance being determined, for example, by the method described in the examples).
[0494] use
[0495] The present invention also provides a use of the composition as described above for forming a coating (preferably a thermal insulation coating) on at least one surface of an article. Preferably, as described above, the surface is a metal surface.
[0496] The invention will now be described with reference to the following non-limiting examples.
[0497] Example
[0498] Material
[0499] The compounds and polymers used in the examples are all commercially available. The compounds and polymers used are summarized in the following table.
[0500]
[0501] Preparation of coating compositions
[0502] The components of the coating composition were mixed in the proportions listed in the table below. The components of the composition are given in the table as % by weight without brackets and % by volume with brackets.
[0503] All liquid parts of component A are mixed in a dissolver. Then one or more suitable fillers are added to the premixed liquid phase of the weighed amount, and are sealed in a container. Then it is homogenized 90 seconds on a Speedmixer running at 1800rpm. For B component, follow the same procedure operation, then component A and B component are transferred to the same container, and mixed at a high speed of 1800rpm for 90 seconds.
[0504] The solids content was calculated based on information provided by suppliers regarding the solids content of their products.
[0505] The VOC is less than 0.5 g / L. The coating composition is substantially free of solvents.
[0506] Preparation of samples for testing
[0507] For thermal conductivity testing, liquid coatings were poured into round silicone molds (60 mm diameter) to depths of 10 mm and 20 mm and then allowed to cure (24 hours at 22°C, 5 days at 60°C, 24 hours at 22°C).
[0508] For the heat reduction test, steel plates (3 mm thick, carbon steel, Sa 2 1 / 2 ) were placed into a suitable silicone mould and coated with the mixed liquid coating. The coating thickness (wet and dry) was 12 mm.
[0509] By making the T-shaped steel (carbon steel, Sa 2 1 / 2 , 1 cm thick, L×W×H 10×11×14 cm) was placed in a 3D printed mold (with 15 mm clearance to all sides) for coating of the T-profile. The premixed composition to be studied was poured into the mold and allowed to cure (24 hours at 22°C, 5 days at 60°C, and 24 hours at 22°C).
[0510] For the sag test, steel panels were placed in a suitable silicone mould and coated with the mixed liquid coating. The thickness of the coating (wet and dry) varied from 1 mm to 15 mm.
[0511] Remove all molds before testing.
[0512] Spraying
[0513] The coating compositions in the following spray examples were sprayed using the following equipment and conditions.
[0514] Components A and B were heated to 65°C in two different pressurized tanks (4.5 bar (65 psi)). Two airless supply pumps (punch assisted feed plate) were used. A metering pump was also used to ensure that the appropriate volume ratio of each component was delivered (metering pump pressure 200-320 bar (2900-4000 psi)). An inline heater was used to ensure that the temperature of the components was within the appropriate range (inline heater temperature, component A was 45°C, component B was 35°C). The size of the nozzle orifice was 27-35 (inch / 1000)), and the temperature at the nozzle was 50°C-60°C. The coating composition was sprayed, and the wet film thickness reached 75mm without any coating sagging.
[0515]
[0516]
[0517] Test Method
[0518] Use a ruler or calipers to measure coating thickness.
[0519] • Thermal conductivity (W / mK) was tested on a FOX50 apparatus from TA instruments according to ASTM C518 and / or C177.
[0520] Heat reduction (°C / mm) is measured by comparing the temperature on the steel panel surface (beneath the coating) to the temperature above the coating surface (by means of different thermocouples). Heating is performed by placing the coated steel panel on a hot plate set at 180-210°C. The coated steel panel is monitored and any peeling of the coating is reported if it occurs.
[0521] Temperature Variation Test – Cyclic: The coated T-profiles were subjected to the following thermal cycles: 3 hours at 60°C, 2 hours at 40°C / hour, 3 hours at -20°C, 1 hour at 40°C / hour, 2 hours at 20°C, 1 hour at 40°C / hour, repeat the cycle. Monitor and visually inspect the samples. When cracks are observed, stop the test. If no cracks are observed, test the samples for 1 month.
[0522] Thermal shock testing is performed by keeping the coated T-profiles in an oven set at 150°C for 16 hours and then directly transferring the samples to a climate chamber set at -20°C and keeping them there for 2 hours. The T-profiles are visually inspected and cracks are reported. If cracks are found, the result is reported as "failed".
[0523] Sag resistance is tested by placing a steel plate on the bottom of a silicone mold, allowing for different thicknesses of coating. The mold is filled with the composition to be tested and immediately placed vertically. A spatula is used to draw a horizontal line down to the bare steel. The test samples are then cured for 16 hours at 23°C and 50% RH. The samples are visually inspected to determine sagging of the coating. Unless otherwise specified, the maximum coating thickness at which no sagging is observed is reported.
[0524] Calculate the density of the coating based on the density of each component related to its mass / volume percentage in the coating.
[0525] The test results are also listed in the following table, where CE stands for comparative example.
[0526]
[0527]
[0528] The coatings of the present invention (Examples 1 and 2) exhibited an ideal balance of properties. The coating compositions were sprayable and dry in an acceptable time at room temperature. The coatings exhibited an ideal low thermal conductivity level and high heat reduction level and did not deteriorate during temperature change testing, i.e., did not peel or crack when the temperature was changed, whether the temperature change was rapid or gradual. In contrast, comparative coatings (CE1 and CE2) that did not contain a mixture of hollow, glass, spherical filler particles and hollow, organic filler particles exhibited peeling or cracking in the tests performed.
[0529] Similarly, the coatings of the present invention (Examples 1 and 2) exhibited better performance than a comparative coating (CE3) comprising a mixture of hollow, glass, spherical filler particles and hollow, organic filler particles but having a lower volume ratio of glass to organic filler particles of 0.71:1 (referenced to 3.6:1 and 1.8:1 in Examples 1 and 2, respectively). As discussed above, Examples 1 and 2 produced coatings that did not degrade during temperature change cycles, i.e., did not peel or crack when the temperature was changed in the thermal shock test, while the coating of CE3 failed the same test.
[0530] Another important property of coating compositions, particularly those applied to non-horizontal surfaces, is their ability to resist sagging. Thicker coatings tend to sag more easily than thinner coatings. However, to achieve thermal insulation, it is generally necessary to build up thicker coatings, e.g., 10-15 mm, and the less coating required to achieve the desired thickness, the better. A number of different coating compositions were tested for their resistance to sagging.
[0531] Coating compositions similar to Examples 1-3 and CE1-3 were prepared by additionally including a thickener, here Examples 1-1, 2-1, 3-1, CE1-1, CE2-1 and CE3-1. The results of the sag test of the resulting compositions are shown below in Table 2. The coating compositions of the invention exhibit strong sag resistance, which is advantageous because it means that the coating can be applied in thicker layers.
[0532] Additionally, additional coating compositions 4-8 and CE4-6 were prepared and tested. The results are shown below in Table 3. The results show that the coating compositions of the present invention provide desirable low thermal conductivity levels as well as sag resistance.
[0533]
[0534]
[0535]
[0536] The results in Table 3 show that the coating compositions of the present invention are resistant to sagging. For example, when the coating composition of Example 5 was applied at a thickness of >10 mm, no sagging was observed when it was placed vertically. This is very advantageous because it means that the coating can be applied in a smaller number of thick coats. In comparison, CE4 lacking a thickener, CE5 lacking a thickener and hollow, organic filler particles, and CE6 lacking a thickener and hollow, inorganic filler particles sagged much more significantly.
[0537] The results show that among the different thickeners tested, the amide wax provides a coating composition with the highest level of sag resistance (Example 5, cf. Examples 6, 7 and 8).
Claims
1. A coating composition comprising: (i) an aromatic epoxy adhesive, wherein the aromatic epoxy adhesive is selected from bisphenol epoxy adhesive, resorcinol diglycidyl ether, novolac epoxy adhesive, and any hybrid or mixture thereof; (ii) a curing agent that cures at ambient temperature, the curing agent being an amino-functional curing agent; (iii) hollow, inorganic, spherical filler particles comprising glass and having a Z-average diameter of 1 to 100 μm; (iv) hollow, organic, spherical filler particles comprising poly(meth)acrylate, polystyrene, polyacrylamide, polyurethane, polysiloxane, polyolefin, polyacrylonitrile, nylon, poly(vinyl ester), vinylidene, polyester or copolymers thereof and having a Z-average diameter of 10-150 μm; and (v) thickeners, wherein the total amount of the epoxy-based binder present in the coating composition is 10-60% by weight, based on the total weight of the coating composition, and the volume ratio of the inorganic, spherical filler particles to the organic, spherical filler particles is 1.1:1.0 to 10.0:1.0; and The weight ratio of the hollow, inorganic, spherical filler particles to the hollow, organic, spherical filler particles is 50:2.5 to 50:0.
25.
2. The composition according to claim 1, wherein the aromatic epoxy-based adhesive is selected from the group consisting of bisphenol A-based adhesives, bisphenol F-based adhesives, and hybrids and mixtures thereof.
3. The composition of claim 1, wherein the curing agent is an aliphatic or alicyclic amine or polyamine.
4. The composition of claim 1, wherein the hollow, inorganic, spherical filler particles are composed of glass.
5. The composition of claim 1, wherein the hollow, inorganic, spherical filler particles have a Z-average diameter of 10-50 microns.
6. The composition of claim 1, wherein the hollow, organic, spherical filler particles have a Z-average diameter of 15-120 microns.
7. The composition of claim 1, wherein the Z-average diameter of the hollow, organic, spherical filler particles is greater than the Z-average diameter of the hollow, inorganic, spherical filler particles.
8. The composition of claim 1, wherein the volume ratio of the hollow, inorganic, spherical filler particles to the hollow, organic, spherical filler particles is 5.1:1.0 to 1.2:1.
0.
9. The composition of claim 1, wherein the thickener is an amide wax thickener.
10. The composition of claim 1, further comprising an organosilane adhesion promoter.
11. A method for preparing the composition according to claim 1, comprising mixing: (i) an aromatic epoxy adhesive, wherein the aromatic epoxy adhesive is selected from bisphenol epoxy adhesive, resorcinol diglycidyl ether, novolac epoxy adhesive, and any hybrid or mixture thereof; (ii) a curing agent that cures at ambient temperature, the curing agent being an amino-functional curing agent; (iii) hollow, inorganic, spherical filler particles comprising glass and having a Z-average diameter of 1 to 100 μm; (iv) hollow, organic, spherical filler particles comprising poly(meth)acrylate, polystyrene, polyacrylamide, polyurethane, polysiloxane, polyolefin, polyacrylonitrile, nylon, poly(vinyl ester), vinylidene, polyester or copolymers thereof and having a Z-average diameter of 10-150 μm; and (v) Thickeners.
12. A kit for preparing the composition according to claim 1, comprising: (i) a first container containing an aromatic epoxy-based binder, optionally hollow, inorganic, spherical filler particles, and optionally hollow, organic, spherical filler particles, wherein the aromatic epoxy-based binder is selected from bisphenol-type epoxy binders, resorcinol diglycidyl ether, novolac-type epoxy binders, and any hybrids or mixtures thereof; (ii) a second container containing a curing agent that cures at ambient temperature, optionally hollow, inorganic, spherical filler particles, and optionally hollow, organic, spherical filler particles, wherein the curing agent is an amino-functional curing agent, wherein the hollow, inorganic, spherical filler particles comprise glass and have a Z-average diameter of 1 to 100 μm, and the hollow, organic, spherical filler particles comprise poly(meth)acrylate, polystyrene, polyacrylamide, polyurethane, polysiloxane, polyolefin, polyacrylonitrile, nylon, poly(vinyl ester), vinylidene, polyester or copolymers thereof and have a Z-average diameter of 10-150 μm, wherein the thickener is present in the first container and / or the second container, And wherein the hollow, inorganic, spherical filler particles and the hollow, organic, spherical filler particles are each present in at least one of the containers, and wherein the volume ratio of the inorganic, spherical filler particles to the organic, spherical filler particles is 1.1:1.0 to 10.0:1.0, and the weight ratio of the hollow, inorganic, spherical filler particles to the hollow, organic, spherical filler particles is 50:2.5 to 50:0.
25.
13. A method of providing a coating on a surface, wherein the method comprises: (i) applying the composition according to claim 1; and (ii) curing the composition to form a coating on the surface.
14. A coating on a surface, wherein the coating is formed from the composition of claim 1.
15. Use of the composition according to claim 1 for forming a coating on at least one surface of an article.
Citation Information
Patent Citations
Fire-retardant low-density epoxy composition
CN101124275A
Industrial thermal insulation coating and preparation method thereof
CN102093788A